Methoxy-functionalized porphyrin-based light responsive COFs: Enabling adsorption-co-reduction of Au(III) from wastewater - Xi Zhang; Longfang Ren; Yixi Wei; Baoshuai Wang; Fei Cheng; Taotao Qiang (Desalination, 2026)

Chemotaxonomic significance of chemical constituents from the fruits of Cerbera manghas L - Fei-Hua Yao; Yue-Yao Li; Zi-Jun Yue; Li-Yi Liang; Xue-Ni Wang; Cheng-Hai Gao; Xiang-Xi Yi (Biochemical Systematics and Ecology, 2026)

Integrative exome sequencing and multi-omics analysis elucidates the regulatory role of rare variants in metabolic syndrome - Cheng-Xi Wu; Jin Sang; Qian Xu; Ya Zhan; Shan-Juan Yuan; Yuan-Yuan Ge; Xiu-Juan Yu; Xiao Zheng; Xiao-Feng Wang; Xian-Mei He; Chao-Jie Liu; Yuan Luo; et al. (Functional & Integrative Genomics, 2026)

Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Waste to resource under grinding-flotation combination: The collision of hazardous carbon dross and waste engine oil - Ningning Feng; Lijia Peng; Bin Li; Jieqiang Zhou; Xi Liu; Zhaohui Cheng; Qiang Huo (Minerals Engineering, 2026)

The control of precipitation rate on cadmium enrichment revealed by sphalerite Cd/Fe ratios in the Jinding MVT deposit, China - Yi-Jie Wang; Kai Luo; Jin Hu; Yong Cheng; Jia-Xi Zhou (Journal of Geochemical Exploration, 2026)

Short-time high-intensity ultrasound directly induces soy protein isolate-glucono-δ-lactone gels - Xi Cheng; Tan Hu; Hongchen Su; Yuxin Xie; Yuan Yuan; Hao Hu (Food Hydrocolloids, 2026)

Why Shear Causes More Particle Breakage than Compression: The Role of Contact Fabric and Energy Efficiency - Zong-Lei Dong; Chen-Xi Tong; Yi Pik Cheng; Jin Chang; Sheng Zhang; Daichao Sheng (Computers and Geotechnics, 2026)

Achieving adsorption re-centering via chemically locked Ni3S2@NiSe heterointerfaces for high-performance battery-type supercapacitors - Xiuzhang Zheng; Xi Wang; Peipei Yang; Lejiao Duan; Jianlong Huang; Liang Cui; Wenrong Yang; Xueying Cao; Degang Jiang; Zhenxiang Cheng; Jingquan Liu (Chemical Engineering Journal, 2026)

Process intensification of dilute methane abatement via a novel bidirectional tidal biofilter: Performance and mass-transfer mechanism - Heng Xu; Siyuan Shang; Quan Yuan; Zhiqiang Zuo; Jianbin Wang; Min Zheng; Zhenkang Wu; Xi Cheng; Huijiao Wang; Qi Qiu; Xinyu Zhang; Dawn E. Holmes (Chemical Engineering Journal, 2026)

Constructing hollow tubular nanoreactors with nanoconfined Co sites for ultrafast water purification in Fenton-like reactions - Xi Wang; Yuheng Yao; Yi Yang; Ke Zhu; Song Yang; Huige Cheng; Jianli Huang; Xiao Tan; Kai Yan (Chemical Engineering Journal, 2026)

Macro–mesoscopic damage evolution and constitutive modeling of bio-reinforced weak interlayer zones under cyclic excavation disturbance - Shu-Qian Duan; Jing-Ran Wang; Xi-Qing Jiang; Jie-Cheng Xiong; Shi-Hao Liu; Ding-Ping Xu; Yun-Long Liu; Jing-Wei Zhang; Wei Liu; Chun-Yu He (Bulletin of Engineering Geology and the Environment, 2026)

Integrating physiological and transcriptomic analyses reveal the role of LrDREB2B in thermotolerance of Lycoris radiata - Xin You; Hua Cheng; Xinyu Zhang; Xi Wang; Wenlin Ye; Xuying Wei; Junhuo Cai (Plant Science, 2026)

Pt-K synergy facilitates NOx storage and conversion for enhanced soot oxidation on 3DOM LaAlO3 perovskite - Quanshui Jing; Detao Xia; Xi Zhang; Huanlong Cheng; Gongde Wu; Yongliang Lu; Nengjie Feng; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2026)

Microscopic leaching mechanism of cryolite impurities in coarse carbon products after carbon dross flotation: DFT, MD, and experiments - Yunkang Sun; Wenjie Yu; Shijie Chen; Zhaohui Cheng; Qi Wang; Chunqiang Chen; Jieqiang Zhou; Xupang Liu; Xi Liu; Qiang Huo (Journal of Environmental Chemical Engineering, 2026)

Chain-length-dependent tissue biodistribution of polyethylene glycol oligomers with 9-20 subunits revealed by green UPC2-MS/MS - Xinyue Zhou; Jiale Liu; Hongjie Ju; Si Cheng; Shuang Feng; Yue Deng; Jiarui Zhang; Yalin Xi; Meiyun Shi; Lei Yin (Food Research International, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Polyvinyl chloride microplastics disrupt spatial purification gradients and amplify antibiotic resistance risks in sulfamethoxazole-stressed constructed wetlands - Yu Xiao; Yangqi Liu; Xi Zhang; Jinping Cheng; Pin Gao (Chemical Engineering Journal, 2026)

Underwater electrical shockwave: an emerging pretreatment for efficient extraction of plant bioactives - Jun Xi; Cheng Zhang (Critical Reviews in Food Science and Nutrition, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Retraction notice to “Trehalose restores functional autophagy suppressed by high glucose” [Reprod. Toxicol. 85 (2019) 51–58] - Cheng Xu; Xi Chen; Wei-Bin Sheng; Peixin Yang (Reproductive Toxicology, 2026)

Improved amino acid bioaccessibility, digestibility, and bioactivity in a soy–yeast dual protein system - Pengpeng Sun; Yuan Yuan; Xi Cheng; Wentao Chen; Yuxin Xie; Hao Hu (Food Chemistry, 2026)

Polystyrene microplastics drive chondrotoxicity in osteoarthritis through inducing ER stress and apoptosis via NFKB1 activation - Jingxin Pan; Xi Wang; Ying Gao; Debin Cheng; Jianbing Ma; Zhao Zhang; Zhiyuan Wang (Food and Chemical Toxicology, 2026)

Porous solar evaporator with hierarchical photothermal structure for highly-performance desalination and water remediation - Yuqian He; Chunguang Liu; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Xi Quan Cheng (Chemical Engineering Journal, 2026)

Interface-targeted remineralization enabled by smart ZrO2@Ag/CPP coating on zirconia: Toward antibacterial and pro-mineralizing dental restorations - Lin Wang; Shaochen Su; Dongyang Ma; Weibo Xie; Xi'’ai Zhang; Yinqin Zheng; Tao Zhu; Luxi Yang; Xiuyun Ma; Daiyue Cheng; Longyu Wang (Chemical Engineering Journal, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

A preliminary design method for jacket support structures of high-capacity offshore wind turbines - Renqiang Xi; Haipeng Shan; Meiling Cheng; M. Hesham El Naggar; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Structure evolution and dynamics of covalent kaolinite ionization under alkaline activation for strategic metal dissociation - Muyang Chen; Xi Chao; Li Cui; Yuchao Zhang; Bo Yang; Kezhou Yan; Yanxia Guo; Fangqin Cheng (Resources, Conservation and Recycling, 2026)

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

UV/Na2S2O8 backwashing controls fouling with limited cell viability loss in anammox MBRs: performance and mechanisms - Siyuan Cheng; Qian Zhou; Weijia Xie; Wenming Wang; Jingyu Liu; Zhicheng Jiang; Xi Tang; Chong-Jian Tang (Environmental Research, 2026)

Carboxymethyl chitosan/sodium alginate-based dynamic organic nanocomposite hydrogel for local tumoral targeted therapy - Huazheng Cheng; Bangyu Song; Xueli Zhou; Tongen Meng; Rongqin Xiong; Guangjun Xi; Guoqing Yan (Carbohydrate Polymers, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

The maternal gut microbiota influences myocardial maturation and diastolic function of offspring in mice - Shanshan Li; Yiqiong Zhang; Yang Li; Yuyang Lei; Hao Wu; Peining Liu; Wen Xi; Xiaozhen Zhuo; Pu Huang; Ting Yang; Ting Bai; Juanli Li; et al. (Science China Life Sciences, 2026)

How does artificial intelligence technology promote industrial structure upgrading? The moderating role of environmental regulation - Ling Huang; Xi Chen; Cheng Chen (Environment, Development and Sustainability, 2026)

Debris flow volume prediction model based on a hybrid BP neural network optimized by adaptive weighted average algorithm with spiral search enhancement - Xi Wang; Li Li; Yue Qiang; Chen Cheng; Xinyi Tan; Nanxi Chen; Xing Wang (Acta Geophysica, 2026)

Bioinformatics and experimental insights into the relationship between ferroptosis and fluoride-induced neurotoxicity - Qinyang Qin; Yuhui Du; Xinying Wang; Leizhen Duan; Yi Cheng; Weihua Jia; Wenyi Liu; Xi Yan; Fangfang Yu; Yue Ba; Guoyu Zhou (NeuroToxicology, 2026)

Influence of suspended particulate matter input on phytoplankton community structure in estuarine environments - Xinjie Wang; Yimei Xi; Kuo Fang; Cheng Li; Yongbin Li; Shaofeng Wang; Ran Bi; Zhanyou Chi; Jiashen Tian; Xiangfeng Zeng (Marine Environmental Research, 2026)

Non-linear responses of ecosystem service trade-offs to landscape heterogeneity: implications for spatially targeted landscape management in an urbanizing agricultural basin - Jiman Li; Henghui Xi; Fei Wang; Xue Ding; Xufei Chen; Yu Tao; Conghong Huang; Qin Tao; Xianbo Cheng; Weixin Ou (Landscape and Urban Planning, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Petrogenesis and element enrichment of Miocene leucogranite in the Chongshan Shear Zone, SW China: Constraints from geochronology, geochemistry, and Hf-Sr-Nd isotopes - Liang Huang; Ye Zhou; Zai-Bo Sun; Feng Zhao; Yan Dao; Su-mei Tian; Shu-Cheng Tan; Xue-long Liu; Shi-tao Zhang; Jia-Xi Zhou (Journal of Asian Earth Sciences, 2026)

Engineering phage endolysins and receptor-binding proteins for foodborne pathogen control and detection: A review and AI-driven framework - Zongcheng Wu; Xiaofeng Yu; Honglin Ren; Chunyi Shangguan; Cheng Han; Xi Yang; Shuaihao Qi; Xuepeng Duan; Han Wang; Pan Hu; Yansong Li; Qiang Lu; et al. (International Journal of Food Microbiology, 2026)

APCoTTA: Continual Test-Time Adaptation for semantic segmentation of airborne LiDAR point clouds - Yuan Gao; Shaobo Xia; Sheng Nie; Cheng Wang; Xiaohuan Xi; Bisheng Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dynamic and residual static performance of steel beam-column subframes with extended end-plate connections under elevated temperatures - Kai Qian; Quan Luo; Zhi Li; Xi Lan; De-Cheng Feng (Engineering Structures, 2026)

Experimental Investigation into the Effect of Process Parameters on Borehole Formation in Bedded Shale by Swirling Abrasive Water Jet - Kang Cheng; Zhongwei Huang; Jingru Hu; Jingbin Li; Bing Xi; Tianshu Wang; Huan Li; Gensheng Li (Rock Mechanics and Rock Engineering, 2026)

Highly sensitive m6A electrochemical biosensor based on laser-induced graphene electrodes functionalized with DNA tetrahedron/gold-antibody nanoparticle - Huiyan Cao; Xi Cheng; Li Huang; Haotian Zhang; Ziyi Liu; Wenjun Yang; Song-Mei Liu; Fang Wang (Analytica Chimica Acta, 2026)

Urban compound humid-heat exposure: Health risks, mitigation challenges, and pathways toward integrated adaptation - Cheng Qian; Chang Xi; Li Wang; Lin Guo; Shi-Jie Cao (Urban Climate, 2026)

Viral isolation and genomic characteristics of the first bovine parainfluenza virus type 3 isolated from water buffaloes (Bubalus bubalis) in China - Can Bao; Yunxin Ren; Cheng Tang; Yurong Su; Hua Yue; Xi Chen (The Veterinary Journal, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Hexavalent chromium inhibits testosterone synthesis in bovine testicular leydig cells through mitochondrial damage via BNIP3 - Hongxia Li; Jia Liu; Liwei Huang; Yu Cheng; Guoqing Zhao; Xiaolong Pan; Lijuan Huang; Pengkang Song; Le Zhao; Xuanqi Yu; Juan Xiong; Qing Tian; et al. (Reproductive Biology, 2026)

Numerical investigation of different diameter-to-depth ratios on discharge performance in three recirculating aquaculture tanks - Chenxu Zhao; Yifan Wang; Liangguang Cheng; Yu Xi; Chao Ma; Zhen Ma; Xiaozhong Ren (Ocean Engineering, 2026)

Thermal effects induced by high-intensity ultrasound on the formation of whey protein isolate fibrils - Yuxin Zhao; Tan Hu; Xi Cheng; Yuxin Xie; Arsalan Khan; Youyou Lv; Jingyao Chen; Hao Hu (Food Research International, 2026)

Contribution of various pectin fractions and internal condition to gel formation in wooly peach fruit during cold storage - Xiangwen Fang; Jianfen Ye; Cheng Li; Xi Yang; Jing Li; Yingying Wei; Shu Jiang; Yi Chen; Feng Xu; Xingfeng Shao (Food Chemistry, 2026)

Experimental and numerical investigation on structural damping behavior of corroded Fe-SMA - Yuanmu Li; Zhe-Xi Zhang; Cheng Fang; Guohui Cao; Cuiling Ran; Haihui Ren; Yuelin Zhang (Engineering Structures, 2026)

Plasma-catalytic ammonia synthesis over Ni/Al2O3 catalysts: The combination of experiment, diagnosis and simulation - Xin Zeng; Liguang Dou; Dengke Xi; Xiucui Hu; Shuai Zhang; Shaojun Xu; Cheng Zhang; Tao Shao (Chemical Engineering Journal, 2026)

Decadal changes and drivers of soil and vegetation carbon in the dryland ecosystems of Northwestern China - Yuqing Chen; Haiyang Xi; Meng Zhu; Bin Wang; Wenju Cheng; Xinwei Yin; Yulian Hao; Linbo Qu; Zhehui Wang (CATENA, 2026)

Screening of Lead/Mercury-Tolerant Lactic Acid Bacteria, Development of a Probiotic Beverage from Auricularia auricula, Red Dates, and Nitraria Fruits, and Its Application for Lead Removal - Yingying Wang; Jieru Zhang; Lan Cheng; Yumeng Chang; Shuhong Ye; Huiping Wan; Xi Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

Synergistic enhancement of selenium accumulation in rice: elucidating the role of biochar and selenobacteria in reshaping root microbiome assembly - Yan-Shan Wang; Zhi-Jiang Wang; Yan Wang; Zhan-Tong Ma; Chen-Wei He; Wei-Kang Wang; Jin-Yu Sun; Su-Tao Shi; Cheng-Xi Lu; An-Yong Hu; Hong Mei; Xi-En Long (Plant and Soil, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

DOM-mediated inhibition of ciprofloxacin photodegradation: Dual roles of antioxidant quenching and triplet-state interactions - Jihong Xu; Weiwen Sun; Jiayan Ding; Yong Huang; Xi Chen; Lin Li; Cheng Peng; Lushi Lian; Xiaohong Guan (Water Research, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Experimental investigation on the fire performance of novel multi-scale fiber reinforced UHPC segments - Yao Zhang; Ruanxiang Xiong; Panpan Cheng; Yibo Chen; Weigang Zhao; Kaihang Han; Xi Jiang; Hehua Zhu; Zhiguo Yan (Tunnelling and Underground Space Technology, 2026)

The expanding world of plant NLR pairs - Cheng-Wei Sang; Yan-Mei Zhang; Sai-Xi Li; Jian-Qun Chen; Zhu-Qing Shao (Trends in Plant Science, 2026)

LiDAR remote sensing meets weak supervision: Concepts, methods, and perspectives - Yuan Gao; Shaobo Xia; Pu Wang; Xiaohuan Xi; Sheng Nie; Cheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Sulfonylurea receptor integrates calcium homeostasis and insulin-like peptide signaling to regulate energy metabolism and larval development in Hyphantria cunea - Yue-Cheng Zhao; Rong-Man Gou; Haneef Tariq; Xi-Lin Li; Lian-Sheng Zang; Li-Wen Song (Insect Biochemistry and Molecular Biology, 2026)

Elucidating the pyrolytic mechanisms of clean and safe gas generator 5-amino-1H-tetrazole/SiO2: A comprehensive kinetic and theoretical investigation - Si-Yuan Zhou; Xuan Li; Yuan-Hui Liu; Hao-Tian Zhou; Peng-Cheng Xi; Dan Zhang; Mi Li; Li-Feng Xie (Fuel, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Towards negative-carbon biohydrogen: A dual-function wollastonite strategy for enhanced fermentation and CO2 sequestration - Weiming Li; Can Jin; Huida Duan; Fangcao Li; Zhangxun Huang; Haodong Zhao; Xiaoman Yu; Yimei Xi; Xiangfeng Zeng; Yongfeng Jia; Chi Cheng (Chemical Engineering Journal, 2026)

Dual-module engineering of Saccharomyces cerevisiae for efficient glucose-xylose Co-utilization via secretory xylose isomerase and xylulose transport activation - Liuqing Yang; Yanshu Huang; Xi Chen; Wanli Cheng; Jiashu Liu; Zhengbing Jiang; Huanan Li (Biomass and Bioenergy, 2026)

Asperhydrindane A, a new hydrindane derivate isolated from a mangrove-derived fungi Aspergillus terreus GXIMD 03158 - Yue Jiang; Fan An; Yu-Man Gan; Kai Liu; Yong-Hong Liu; Cheng-Hai Gao; Pei Cao; Xiang-Xi Yi; Meng Bai (Natural Product Research, 2026)

Two new sesquiterpene eudesmanolides from the Croton cascarilloides Raeusch - Tian-Yi Liu; Hong-Li Liu; Xi Jiang; Qiong Liu; Jing-Jie Bai; Ze-Ying Guo; Zheng Zhang; Ji-Hai Shang; Cheng-Shan Yuan (Natural Product Research, 2026)

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Aldometanib attenuates OGD/R-induced cardiomyocyte injury via mitigation of mitochondrial dysfunction - Mian Xie; Jiajia Hao; Chen Chao; Xi Chen; Qiuling Chen; Yao-wang Lin; Jiang-hua Li; Qi-yun Liu; Cheng Liu (Tissue and Cell, 2026)

AUV path planning based on crested porcupine optimizer and improved fuzzy DWA with collision risk assessment - Xi Zhang; Jianbo Wu; Liang Cheng; Qing Wang; Yinglin Ke (Ocean Engineering, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Direct evolution and expression of Tfcut-B3 in Bacillus subtilis for efficient depolymerization of commercial PBAT-based plastics films - Mingliang Zhang; Fanghui Ding; Xi Xiao; Minggen Cheng; Qing Hong; Xin Yan (Journal of Hazardous Materials, 2026)

Integrated optimization of hydrogen refueling stations with green and blue hydrogen production for freight corridors - Yeonkyeong Gina Park; Alireza Yazdiani; Ruochong Zhu; Junchi Xiao; Pufan You; Xi Cheng; Charlle Sy; H. Oliver Gao (Journal of Cleaner Production, 2026)

Physicochemical characteristics, metabolomics, and flavor profiles of giant salamander (Andrias davidianus) liver pastes fermented with Lactobacillus plantarum, Bacillus coagulans, and their mixtures - Wengang Jin; Kaiqi Cheng; Jiani Liu; Yucheng Liu; Linjie Xi; Wen Su; A.M. Abd EI-Aty; Ruichang Gao (Food Research International, 2026)

Decoding the core microbiota during liquor fermentation of sauce-aroma baijiu: Advances in the characteristics of core microbial communities and their regulatory strategies - Cheng Wu; Xiuting Li; Bo Wan; Feng Hu; Jianfeng Hu; Hu Lu; Xi Chen; Weiwei Li; Diqiang Wang; Baoguo Sun (Food Research International, 2026)

Construction of lignin–metal polyphenol networks and their application in smart paper-based active packaging: Multifunctional materials with both antioxidant and UV-shielding functions - Lirong Lu; Jiatian Zhu; Jingpeng Zhou; Xi Cheng; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Food Chemistry, 2026)

Synergistic inactivation of lycium polyphenol oxidase by acidic electrolyzed water combined with vacuum pulsed drying: Mechanism and color retention study - Bona Chai; Zhengxu Yang; Bo Cheng; Jiaxin Xi; Peng He; Ningbo Kang (Food Bioscience, 2026)

Thermal effects induced by high-intensity ultrasound cavitation on soy protein isolate: Structural modulations and gelation behaviors - Yuan Yuan; Tan Hu; Xi Cheng; Hongchen Su; Yuxin Xie; Hao Hu (Food Hydrocolloids, 2026)

Quantifying and Predicting Heterogeneity in Marine Clastic Reservoirs Through Machine Learning: Methodology and Applications - Yu Ye; Chao Cheng; Jie Chen; Xiangjun Liu; Xi Li; Guo Chen; Liang Cheng; Jie Fang; Peiyan Li (Natural Resources Research, 2026)

Vertical distribution, source apportionment, and ecological risk assessment of heavy metals in columnar sediments of Honghu Lake: a coupled SOM–PCA–PMF approach - Yiting Cheng; Yuanzheng Liu; Xi Liu; Xue Jiang; Xiaoguo Chen; Zhi Wang (Environmental Geochemistry and Health, 2026)

Epitranscriptomic regulation of NVP-BEZ235 resistance in ccRCC via the YTHDF3-SYNM regulatory pathway - Ruiang Wang; Cheng Lu; Erchang Shen; Xi Zhang; Xinchi Xu; Xiaoyang Cao; Tian Rao; Xiaohan Ren; Yiyang Liu; Chen Xu; Xiaoxiang Wang (Genes & Genomics, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Asymmetric Shifts in Precipitation Alter Nitrogen Use Strategies in Global Croplands - Jinglan Cui; Yujing Gao; Luxi Cheng; Xi Zhang; Ouping Deng; Miao Zheng; Zhongrui Xie; Hans J. M. van Grinsven; Lorenzo Rosa; Baojing Gu (Global Change Biology, 2026)
Global warming intensifies regional precipitation imbalances that disrupt cropland nitrogen cycling and threaten food security. Here, we show that global croplands respond asymmetrically to future precipitation change. Under a middle of the road scenario for 2050, 78% of croplands are projected to become wetter, increasing yields by 15% but raising nitrogen losses by 45%. The remaining 22% that become drier would experience a 29% decline in yields and a 25% rise in nitrogen losses. Nitrogen use efficiency declines by 3%–14% worldwide because both wetter and drier conditions reduce plant uptake or accelerate losses. Although altered precipitation increases global crop production by 8%, the accompanying 43% rise in nitrogen losses may compromise long term sustainability. Subtropical and tropical regions between 30° N and 30° S emerge as disruption hotspots. Adaptation measures such as optimized fertilizer management and adjusted planting dates could mitigate up to 462 billion USD per year in damages linked to nitrogen losses. These results highlight the need for adaptive strategies to secure food production and environmental sustainability under asymmetric precipitation change.

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Biological activity of alkaloids from kenaf bast fibres - Xiangyuan Feng; Lifeng Cheng; Guoguo Xi; Ke Zheng; Zhenghong Peng; Fengbo Han; Qi Yang; Shengwen Duan (Natural Product Research, 2026)

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

Supplementation of cGMP during in vitro culture enhances the developmental competence of sheep embryos - Jia Hao; Si Ouyang; Yubing Wang; Lei Cheng; Dayong Chen; Chunjuan Qiu; Riga Wu; Yongji Xie; Jianhui Tian; Lei An; Guangyin Xi (Small Ruminant Research, 2026)

Genomic analysis of Sulfitobacter sp. M13 reveals its role in dimethylsulfoniopropionate (DMSP) metabolism - Chen-Xi Li; Min Zhang; Meng-Xue Yu; Qing-Yu Dong; Yu Wang; Yu-Fei Ding; Shu-Yan Wang; Jin Cheng; Jing-Yu Zhang; Chun-Yang Li (Marine Genomics, 2026)

Investigation into the impact of cold plasma pretreatment on the pyrolysis reaction characteristics of cellulose - Bin Hu; Guan-Zheng Zhou; Shou-Gang Wei; Zhan-Jun Cheng; Ji Liu; Kai Li; Zhen-Xi Zhang; Qiang Lu (Fuel, 2026)

Synergizing root growth and carboxylate release enhance seed yield in maize-soybean intercropping on acidic karst soils - Cheng-Xi Yi; Yi Jin; Long-Gui Li; Yu-Mei Wang; Yu Dai; Qiao Zhu; Xiao-Li Wang; Yinglong Chen; Xiao-Min Wu; Jin He; Sanwei Yang (Field Crops Research, 2026)

Optimized one-step pyrolysis synthesis of zinc-modified sludge biochar for enhanced perfluorooctane sulfonate removal from water - Muzi Li; Ranbin Liu; Xiaodi Hao; Dongye Zhao; Xi Cheng; Jian Pan; Tianyuan Xu; Shuting Tian; Yangmo Zhu (Environmental Research, 2026)

Promoting the ionic conductivity and self-healing ability of micro-Si anode via a versatile crosslinker of Al(H2PO4)3 - Yang-Ning You; Shu-Hao Guo; Tao Li; Yu-Jun Bai; Xi-Cheng Ma (Chemical Engineering Journal, 2026)

Secondary information encryption via programmable anthracene-based hydrogels - Chuchu Cheng; Dong Wang; Xingyuan Lu; Minmin Fan; Xi Zhang (Chemical Engineering Journal, 2026)

Bioinspired lignin-based coatings for durable and photothermal antibacterial surfaces - Cheng Wang; Bowen Ran; Kexin Li; Xiaodong He; Jing Li; Yunjie Xiang; Kun Xu; Xi Rao; Selvakumar Murugesan; Valentim A.R. Barão; En-Tang Kang; Liqun Xu (Chemical Engineering Journal, 2026)

Synergistic Mg/Cu co-doping toward optimizing phase transitions across the full voltage window in P2-type sodium-ion cathodes - Xinglong Liang; Yutong Nong; Weigang Wang; Cheng Peng; Yi Tian; Jingyi Zhang; Xiaowei Wang; Jiuqing Liu; Xi Li; Jiafeng Zhang; Ji Liang (Chemical Engineering Journal, 2026)

Unraveling and overcoming ammonium toxicity in haloalkaliphilic methanotrophs for economic biomanufacturing and methane mitigation - Haili Zhang; Zixi Gao; Xi Xiao; Minggen Cheng; Qiang Fei; Xin Yan (Bioresource Technology, 2026)

Floral fragrance in sweet osmanthus majorly repels pollen feeders - Hui-Hui Feng; Cheng-Xi Tan; Shao-Cheng Huang; Shuang-Quan Huang (Science China Life Sciences, 2026)

Reservoir property estimation of interbedded sandstone and shale layers using segmented 3D rock-physics templates - Jing Ba; Xi-Ya Ba; Hong-Jing Dong; Jun-Wei Cheng; Cong Luo; Zhi-Fang Yang; Meng-Qiang Pang; Wen-Hui Tan (Applied Geophysics, 2026)

BACH2 ameliorates cell apoptosis and autophagy as a molecular switch of BCL-2/Beclin-1 complex in myocardial infarction - Xiaolin Wang; Hongyuan Zhang; Xi Liu; Xinjie He; Mengying Cao; Wenhao Wang; Chao Yin; Lin Li; Shijun Wang; Cheng Yang; Pan Gao; Yunzeng Zou (Apoptosis, 2026)

The Fully Interactive Martian Dust Cycle Simulations by the GoMars Model - Shuai Liu; Li Dong; Xiangyu Xi; Xuan Cheng; Juanjuan Liu; Ye Pu; Yiyuan Li; Hongbo Liu; Mingyu Liu; Wei Xue; Junji Cao; Bin Wang (Advances in Atmospheric Sciences, 2026)

Integrating CO2-EOR and Sequestration via Assisting Steam Huff and Puff in Offshore Heavy Oil Reservoirs with Bottom Water - Guodong Cui; Kaijun Yuan; Haiqing Cheng; Quanqi Dai; Xi Chen; Rui Wang; Zhe Hu; Zheng Niu (Journal of Marine Science and Engineering, 2026)
CO2-assisted steam huff and puff is an effective method to improve oil recovery and store CO2 in heavy oil reservoirs. However, few studies focused on complex geological formations, such as bottom water. The bottom water condition not only complicates the process of oil production and CO2 sequestration, but also makes migration and distribution of oil, water and CO2 unclear. In this paper, a numerical geological model of an offshore heavy oil reservoir with bottom water is established to analyze the influence of bottom water on injection and production parameters, oil recovery and CO2 storage capability under vertical and horizontal well layouts. The results show that the bottom water could maintain the formation pressure, but reduce the steam chamber radius and heavy oil utilization area, increase water production and decrease the oil–water ratio. CO2 could enhance oil recovery in the bottom water reservoir. Oil development indicators of the horizontal well are higher than the vertical well. Meanwhile, CO2-assisted steam huff and puff use in the bottom water reservoir can create a high-pressure and -temperature environment to make CO2 supercritical, as it has better CO2 storage capability and efficiency. The CO2 storage efficiency of the horizontal well is 63% larger than the vertical well. Thus, the horizontal well layout should be used as a priority if bottom water presents. Conducted analysis of bottom water formation sensitivity parameters shows that the advantageous formation conditions are high oil saturation, porosity of 0.2–0.4 and permeability of 2000–3000 mD. The influence degrees of each formation parameter were evaluated as well.

Plankton diversity and its application in water safety evaluation under the background of compound pollution—A case study of Qiantang River - Xi-Long Zhang; Cheng Ye; Jian-Ming Jiang; Sha Shi; Hui Liu; Wen-Jun Hong (Environmental Monitoring and Assessment, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Integrated risk assessment of coastal red tides in China: A 90-year county-level framework combining hazard and vulnerability - Zheng-Xi Zhou; Chun-Hui Wu; Qing-Chun Zhang; Ren-Cheng Yu (Ocean & Coastal Management, 2026)

Experimental study of operating characteristics of a novel rack-level hybrid cooling system for data centers - Tongzhi Yang; Xi’an Liu; Yifan Zhao; Weixing Yuan; Hao Cheng; Kexian Ren (International Journal of Refrigeration, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

Construction of a GdVO4-In2O3 n-n heterojunction enables ppb level triethylamine detection at low temperatures - Yi-Cheng Geng; Xiang-Bing Li; An-Qi Wang; Bing-Yi Xi; Qian-Qian Zhang; Li-He Yan; Fa-Ming Li; Wei-Dong Zhu (Chemical Engineering Journal, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Efficient production of epsilon-poly-l-lysine from lignocellulosic hydrolysates via zeolite-based solid-state fermentation - Xin Zeng; Siyu Tong; Qiran Diao; Zhiwei Su; Chen Zhang; Ya Cheng; Xi Chen; Yufei Chang; Mingzhi Zhu (Bioresource Technology, 2026)

Acid-catalyzed ethanol depolymerization of Chaenomeles sinensis lignin for enhanced phenolic antioxidants and biodiesel stabilization - Xi-Chuang Cheng; Zhao Qin; Qi-Wei Zhang; Yuan-Qing Luo; Hua-Min Liu (Bioresource Technology, 2026)

Decoding temperature and NaOH concentration effects on environmental footprints for sustainable lignocellulosic biorefining through systematic LCA - Xinyi Du; Taotao Cheng; Qiulan Xie; Qianyi Xiao; Geng Luo; Lili Dong; Penghao Ye; Guangli Cao; Xi-Zhi Niu; Shanshan Yang (Bioresource Technology Reports, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Succession alters carbon cycle regulation by shifting environmental factors and microbial community dominance in arid soils - Xiaonan Li; Kai Zhang; Fengchang Wu; Xiaoli Zhao; Xi Cheng (Applied Soil Ecology, 2026)

Insights into land deformation processes in the Yellow River Delta (China) from synthetic aperture radar interferometry time series and machine learning - Pengfei Ge; Mi Chen; Roberto Tomás; Hui Liu; Kailun Fan; Xi Cheng; Xingyuan Fu; Shuang Wang (Advances in Space Research, 2026)

On the Specific Status of Rhinogobius zhoui (Gobiiformes, Gobiidae) with mtDNA Characterization - Shuang-Xi Jia; Zi-Xuan Wu; Chang-Hu Lu; Cheng-He Sun (Biochemical Genetics, 2026)

A monogamous male's dilemma: Managing two females and parental care in white‐faced plovers - Boya Xie; Xi Lin; Xiaotong Niu; Heiman Ho; Xinlei Liu; Xin Lan; Zitan Song; Yachang Cheng; Yang Liu (Ecology, 2026)

Development of a Novel Experimental System for Simulating the Whole Grouting Process of Diffusion–Filling–Splitting in Deep Rock Engineering - Xia-Ting Feng; Xi-Fan Li; Yang-Yi Zhou; Cheng-Xiang Yang; Tian-Xiang Song (Rock Mechanics and Rock Engineering, 2026)

Millmerranones G, a meroterpene isolated from a mangrove-derived fungus Aspergillus sp. GXIMD 03004 - Guang-Ping Cao; Guo-Qiang Huang; Guang-Ying Chen; Xiang-Xi Yi; Xue-Sheng Wang; Feng-Jiao Wei; Cai-Qiong Zhu; Cheng-Hai Gao; Yong-Hong Liu; Meng Bai (Natural Product Research, 2026)

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

A novel bathymetric mapping framework integrating indirect inversion of ICESat-2 and multi-source remote sensing data - Zijia Wang; Sheng Nie; Cheng Wang; Jian Zuo; Xiaohuan Xi; Xiaolin Bian; Xiaoxiao Zhu; Bisheng Yang (Remote Sensing of Environment, 2026)

PpERF.E3 regulates peach fruit ripening and softening by mediating ethylene biosynthesis and cell wall degradation - Xingzhen Zhang; Tongyang Kang; Lijun Cao; Qianjin Zhan; Yuting Xu; Jingwen Zhu; Xuyang Zheng; Xi Cheng; Yanan Hu; Caiping Zhao (Postharvest Biology and Technology, 2026)

Efficient lithium recovery from aluminum electrolytic slag via HCl solution: Leaching behavior and mechanism - Xi Chao; Guannan Li; Hefeng Yuan; Li Cui; Lijuan Wang; Fangqin Cheng (Minerals Engineering, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Low-temperature sludge pretreatment accelerates partial nitrification start-up and reveals hydroxylamine-induced instability at low ammonium concentrations - Kai-Yue Dong; Chao-Xi Yang; Ning Gao; Shi-Xu Wang; Ruo-Tian Gao; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Phycosphere bacterial communities mediate arsenic accumulation and speciation in coastal macroalgae: Evidence from field investigation - Cheng Li; Hanyu Sun; Yimei Xi; Yongbin Li; Xinjie Wang; Zhangxun Huang; WeiMing Li; Xiangfeng Zeng; Yongfeng Jia (Journal of Hazardous Materials, 2026)

Development of a highly responsive and stable pH-responsive smart film using co-pigmentation: Preparation, characterization, and application for fish freshness monitoring - Xi Hu; Weidong Zhang; Xin Qi; Lanlan Cheng; Mingyue Shen; Huiliang Wen; Jianhua Xie (Food Packaging and Shelf Life, 2026)

Achieving fast reverse intersystem crossing and high electroluminescent efficiencies in TADF emitters with N-phenylphthalimide (PhAI) as electron-acceptor coupled with single electron-donor - Tianlin Cheng; Xi Chen; Daokun Zhong; Jun Liu; Xiong Huang; Yuanhui Sun; Xiaolong Yang; Bo Jiao; Guijiang Zhou (Chemical Engineering Journal, 2026)

Photonic crystal-plasmonic nanoantenna coupling biosensor for AI assisted protein biomarker detection - Yu Lu; Qifan Zhou; Binze Teng; Xi Yang; Yan Huang; Cheng Chen; Xiaoyi Lv; Dianhuai Meng; Xiangwei Zhao (Chemical Engineering Journal, 2026)

Ferroelectric-polarization-induced high-rate performance: 120C achievement with porous Na3Fe2(PO4)P2O7 and nano-BaTiO3 composite cathodes for sodium-ion batteries - Luting Kou; Xi Chen; Huimin Liu; Shuoshuo Cheng; Mengting Wu; Min Li; Ying Bai; Yibo Wang; Qian Dong; Jiahui Qian; Shiyu Li; Wei Lu (Chemical Engineering Journal, 2026)

Continuous flow outperforms sequencing batch operation: Mechanistic insights into the enrichment of complete ammonia oxidizing bacteria under low-ammonium, oligotrophic conditions - Wenni Xi; Lei Cheng; Xiaoyu Fang; Xianyang Shi (Bioresource Technology, 2026)

Distribution and recycling of chalcophile elements and consequences for terrestrial resources and environment - Zaicong Wang; Xiang Wang; Zongqi Zou; Kang Chen; Lang Wang; Huai Cheng; Aiqing Ren; Xi Zhao; Jinling Liu; Keqing Zong (Science China Earth Sciences, 2026)

Applying a combination of artificial humic acid and microbial agent to increase rhizosphere soil organic carbon content and maize yield - Yue Yuan; Wentao Li; Qingyu Liu; Xi Zhang; Fan Yang; Zhuqing Liu; Kui Cheng (Plant and Soil, 2026)

The role of circulating metallothionein 1 in voriconazole-associated hepatotoxicity - Xiaowen Wang; Lina Wang; Xi You; Changsheng Jia; Qian Wang; Lin Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Motor Cortex VIP Interneurons Participate in Dexmedetomidine-Associated Sleep Modulation - Wei Wang; Hanmei Zhang; Tianqi Zhang; Qianyi Huang; Jiaxin Li; Nuo Li; Yue Xi; Xiaohan Yang; Fen Wang; Jun Tu; Dongmei Ji; Juan Cheng (Molecular Neurobiology, 2026)

Development and Experimental Validation of an Ice Air Jet with a Laval Nozzle for Coal Breakage and Permeability Enhancement - Jingru Hu; Hou Zhong; Kang Cheng; Shihao Zhang; Bing Xi; Huan Li; Gensheng Li; Jingbin Li; Zhongwei Huang; Ke Hu (Rock Mechanics and Rock Engineering, 2025)

Triterpenoids and sterols from Pseudocydonia sinensis fruits and their anti-inflammatory activity - Qi-Qi Zhao; Na-Na Chen; Shuan-Cheng He; Jiang-Xian Chen; Young-Ho Kim; Xi-Tao Yan; Ya-Tuan Ma (Natural Product Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hierarchically ordered CNTs encapsulating Ni-polyoxometalate with exterior Fe-porphyrin enable vectorial charge transfer for efficient CO2 photoreduction - Bonan Li; Mengxue Chen; Xi Zhang; Weize Sun; Haoshan Cheng; Xiao Fang; Khalid Umer; Yanfang Yang; Yuanyuan Li; Yong Ding (Science Bulletin, 2025)

Chalcophile element contents of coeval volcanic rocks derived from heterogeneous mantle beneath North China Craton - Lang Wang; Zaicong Wang; Xiang Wang; Keqing Zong; Jianwei Li; Yutian Lei; Jingliang Guo; Yanhong Liu; Chongjin Pang; Haidong Zhang; Tao He; Zhaochu Hu; et al. (Lithos, 2025)

Efficient biomass fractionation for levulinic acid production from rice husk - Xi Cheng; Qingge Feng; Dachao Ma; Yuan Qi; Lin Feng; Fanghong Qin; Xiaodie Cheng; Xu Zeng (Journal of Environmental Chemical Engineering, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Integrating peroxidase-mimicking MOF-based composite nanozymes with molecular imprinting for dual-mode thiamphenicol sensing in animal-derived foods - Shujuan Chen; Xi Cheng; Wenjing Wang; Minglin Ye; Yuan Cai; Fujia Zhong; Likou Zou; Jianlong Li; Shuliang Liu; Kaidi Hu; Aiping Liu (Food Chemistry, 2025)

Chinese herbal feed additives in aquaculture: Disease resistance and antioxidant functions - Xinyue Liu; Wenjing Ma; Wenting Zeng; Xi Cheng; Yi Huang; Yuhang Hong (Fish & Shellfish Immunology, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Boron promoted Pt/Al2O3 catalysts with superior stability for Methylcyclohexane dehydrogenation - Voon Huey Lim; Hossein Akhoundzadeh; Zheng Wang; Shenghui Zhou; Chao Wu; Mohammadreza Kosari; Chi Cheng Chong; Xin Zhao; Shibo Xi; Rong Xu (Chemical Engineering Journal, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Tightly Interfaced Heterojunction of In2O3@TiO2: A Facile Synthesis of MOF-on-MOF Derived In2O3@TiO2 and their Enhanced Performance in Photodegrading Tetracycline Under Visible Light Irradiation - Xia Zhang; Mengqin Zhou; Xiu Wan; Xi Liu; Shixiong Hao; Chunru Cheng; Zhongming Xiao; Yongfan Wang (Water, Air, & Soil Pollution, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

The 1357 bp deletion in β-thalassemia: molecular profiling and hematological characterization in a Guangxi cohort - Youqiong Li; Tianjie Zhou; Lihua Ye; Liang Liang; Shufu Cheng; Lihong Zheng; Xi He; Peixing Wan; Tongfeng Huang (Molecular Biology Reports, 2025)

Complete mitochondrial genome sequence of Nannostomus eques and comparative analysis with Nannostomus beckfordi - Xian-Ru Li; Cheng-He Sun; Yi-Jing Zhan; Shuang-Xi Jia; Chang-Hu Lu (Molecular Genetics and Genomics, 2025)

How the Carbon Neutrality Process Moves Forward: a Global-scale Evaluation from Past To Future - Yicheng Yang; Zefeng Qi; Hongxuan Fu; Shuan Peng; Nihed Benani; Xi Cheng; Jian Lin Chen; Pingjian Yang; Guozhu Mao (International Journal of Environmental Research, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

A porous SERS microneedle for multiplex detection of glucose, uric acid, and cholesterol in interstitial fluid - Geng Zhu; Yang Wang; Xi Yang; Cheng Chen; Xiaoyi Lv; Yan Huang; Xiangwei Zhao (Analytica Chimica Acta, 2025)

A highly sensitive magnetic separation-assisted electrochemical sensor for detection of m6A-microRNA-17–5p based on rolling circle amplification and N3-kethoxal labeling strategy at LIG electrodes - Xi Cheng; Jingyi Guo; Huiyan Cao; Haiyue Bi; Shouquan Dong; Hongling Wang; Xiaocheng Weng; Fang Wang (Analytica Chimica Acta, 2025)

Development of a Private Cloud Platform for Distributed Logging Big Data and Its Application to Geo-Engineering Evaluation of Geothermal Fields - Xi Cheng; Hai-cheng Fu; Jun He (Applied Geophysics, 2025)

Variability of Springtime Coastal Polynyas over the Ross Sea and Its Impact on the Following Sea-Ice Evolution - Zixin Wei; Shaoyin Wang; Jiping Liu; Xi Zhao; Teng Li; Xiao Cheng (Advances in Atmospheric Sciences, 2025)

Mauritone A, a new polyketide from a fungal-bacterial symbiont Aspergillus spelaeus GXIMD 04541/ Sphingomonas echinoides GXIMD 04532 - Jie Yang; Fei-Hua Yao; Shu-Fen Xu; Jie-Yu Shi; Xiao-Yan Li; Xiang-Xi Yi; Cheng-Hai Gao (Natural Product Research, 2025)

Corrigendum to “Modeling and assessing the impacts of climate change on groundwater recharge in endorheic basins of Northwest China” [Sci. Total Environ. 918 (2024), 170829] - Wenju Cheng; Qi Feng; Haiyang Xi; Xinwei Yin; Celestin Sindikubwabo; Baiting Zhang; Yuqing Chen; Xinyue Zhao (Science of The Total Environment, 2025)

Development and quality analysis of low GI composite buckwheat steamed bun - Ting Zhang; Jiayue Zhang; Wanzeng Li; Xinyuan Hu; Huiru Cheng; Kang An; Jingwen Wang; Dan Yang; Hua Li; Jun Xi; Kunlun Liu; Zhifeng Zhang; et al. (Journal of Cereal Science, 2025)

Petrogenesis and tectonic significance of low-δ18O A-type granites in Nianzishan, Great Xing’an Range, NE China - Wen-Ting Zhang; Ying Wei; Ming-Xing Ling; Yi-Bo Zhao; Xi-Hui Cheng; Tian-Chu Chen (Journal of Asian Earth Sciences, 2025)

Characterization and formation process analysis of peach fruit woolliness under low-temperature storage - Jiajia Xu; Jianfen Ye; Cheng Li; Yuqing Guo; Weixiang Jiang; Xi Yang; Yingying Wei; Shu Jiang; Yi Chen; Xingfeng Shao (Food Chemistry, 2025)

A novel gelation method of food biomacromolecule protein induced by high-intensity ultrasound directly - Xi Cheng; Hongchen Su; Yuxin Xie; Arsalan Khan; Yuan Yuan; Yuxin Zhao; Hao Hu (Food Chemistry, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

Enhancing the CO2 adsorption performance on 13× zeolite by optimising K+ ion-exchange degree - Lizhuo Wang; Qi Cheng; Zhiqiang Zhao; Shibo Xi; Ying Shu; Chunjing Su; Namuersaihan Namuersaihan; Jun Huang (Chemical Engineering Journal, 2025)

Scalable electrode substrates for environmentally stable and flexible humidity sensors - Zhenyu Gong; Zibo Chen; Fangzheng Xi; Bo Liu; Yunfa Si; Jie Wen; Xiaodong Ji; Mingyang Tanwei; Cheng Chen; Peng Li; Shaowen Cao; Geng Wu; et al. (Chemical Engineering Journal, 2025)

Hierarchical Janus sponge evaporator functionalized with liquid-like PDMS molecular brushes for efficient and sustainable solar evaporation and electricity generation - Siying Guan; Taolin Zhang; Shouzheng Jiao; Rongxue Xi; Rui Ma; Chenshun Hu; Yuwei Hao; Zhicheng Sun; Zhongjun Cheng (Chemical Engineering Journal, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

Intercropping sunflower with amaranth to remediate cadmium-contaminated agricultural land: performance and mechanism - Zhuo-hui Wu; Feifan Wang; Mai Ye; Jingru Zhang; Zhiyi Li; Yunrong Xi; Rongzhou Jin; Yanying Li; Zhipeng Chen; Ye Wu; Ting Huang; Qijie Cheng; et al. (Plant and Soil, 2025)

Climatological characteristics of tropical cyclones simulated in the global-regional integrated forecasting system (GRIST) model - Xi Cheng; Xinyao Rong; Yi Zhang; Yuqing Wang; Jian Li; Jing Xu (Climate Dynamics, 2025)

Low-potential pyrene-coordinated MOFs and CoSOH nanosheets: An electrochemiluminescence energy resonance transfer system for aflatoxin B1 detection - Cheng Tan; Jiayuan Nie; Jingjing Xi; Xiao Mei; Kang Wu; Anping Deng; Xinjian Feng; Jianguo Li (Analytica Chimica Acta, 2025)

Broadening the Na+ diffusion degree of freedom to unlock a rapid sodium storage potential in fluorophosphate cathode - Hong Yu; Jinjin Wang; Hongbo Jing; Chao Wu; Erhai Hu; Shibo Xi; Xiaomei Wang; Zhiyu Fang; Xing-Long Wu; Qinghua Liang; Weihong Qi; Qingyu Yan; et al. (Science Bulletin, 2025)

Impact of pretreatment methods on hydrogen and ethanol co-production from brown algae: Energy recovery and cost analysis - Zhongliang Shi; Chi Cheng; Mengyang Bian; Weiming Li; Yimei Xi; Shuhua Yao; Xiangfeng Zeng; Yongfeng Jia (Journal of Environmental Chemical Engineering, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Chemical characterization and causes of differences in surface sediments of sand dunes in northern China under wind-water composite effects – A case study of the Kubuqi Desert - Cheng Xi; Hejun Zuo; Min Yan; Yu Yan (Geomorphology, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

Enhanced copper adsorption by polyamide and polylactic acid microplastics: The role of biofilm development and chemical aging - Xinfeng Cheng; Zhifu Yang; Ke Ji; Zhiyuan Hu; Yilong Xi; XianLing Xiang (Environmental Research, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Chemotaxonomic significance of chemical constituents from Ligia exotica, sea slater - Yue-Yao Li; Fei-Hua Yao; Qian Han; Jin-Li Luo; Xin-Yue Li; Cheng-Hai Gao; Xiang-Xi Yi (Biochemical Systematics and Ecology, 2025)

Deep learning-based prognostic assessment of polyploid giant cancer cells and mitotic figures in liver cancer - Jingying Yang; Cuimin Chen; Qiming He; Jiayi Li; Houqiang Li; Jing Peng; Junru Cheng; Meihui Li; Xiaozhuan Zhou; Yonghong He; Tian Guan; Xi Li; et al. (Medical & Biological Engineering & Computing, 2025)

Transcriptomic Analysis of Litopenaeus vannamei: Understanding Salinity Adaptation Mechanisms in Freshwater Environments - Xuenan Li; Xi Cheng; Xilin Dai (Marine Biotechnology, 2025)

In vitro inhalation bioaccessibility for PM10-bound neonicotinoids: method development, effects of hydrophobicity, and its implication in health risk assessment - Hui Liu; Mei-Yang Zheng; Cheng Ye; Rengzong Shu; Xi-Long Zhang; Qi Di; Jin-Jian Ding; Wen-Jun Hong (Environmental Geochemistry and Health, 2025)

Bilayer crown ether-engineered nanofiltration membranes with dual Li+ transport channels for ultra-high Mg2+/Li+ separation from saline lake brines - Ke Liu; Yingjie Xia; Xi Chen; Xiaoke Li; Kun Zhou; Ying Zeng; Guangyong Zeng; Xiaojie Cheng; Zhangyang Luo; Shouliang Yi (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Clarifying the mechanism of AHLs-regulated quorum sensing in reducing N2O emission from the aerobic tank in wastewater treatment plant - Kaiwen Cheng; Wenjiao Sang; Xi Jin; Danni Jia; Qian Zhang; Fangmao Gan; Lei Zou; Shanshan He (Process Safety and Environmental Protection, 2025)

Analysis of spontaneous failure of lithium-ion battery under micromechanical deformation - Chuang Qi; Hongtao Yan; Hao Cheng; Yuemeng Zhang; Chunjing Lin; Siqi Chen; Xi Liu; Li Lao; Yazhou Sun; Qiang Wang (Process Safety and Environmental Protection, 2025)

Maternal and early postnatal antibiotic exposure may increase the risk of autism spectrum disorder with regression - Boli Cheng; Xi Lai; Huan Liu; Si Wang; Xinghui Li; Mei Tan; Juan Liu; Yun He (Neurotoxicology and Teratology, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Thermodynamic simulation on indium enrichment condition in the Huangshaping skarn Zn-Pb system (South China) - Yihan Wu; Yi Zheng; Pengpeng Yu; Yin Huang; Jie Yu; Taiping Zhao; Qiuming Cheng; Xi Chen (Journal of Asian Earth Sciences, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Lactobacillus gasseri LG 2361 from infant feces synergizes with Lactobacillus acidophilus ATCC 43121 to lower lipids in high-fat fed mice - Xi Lu; Xirui Cheng; Guohua Li (Food Bioscience, 2025)

Multifunctional regulation of trace tetra-carboxyl additive for stable Zn anodes in aqueous electrolytes - Xi Cheng; Min Sang; Danying Zuo; Jing Xu; Hongjun Li; Hongwei Zhang (Chemical Engineering Journal, 2025)

Two new cadinane-type sesquiterpene glycosides from Dendrobium findleyanum - Zi-Xi Lin; Zhong-Quan Cheng; Dan Yang (Natural Product Research, 2025)

Coupling microwave irradiation with peroxymonosulfate activation for sludge deep dewatering via enhancing internal bound water removal - Chao-Xi Yang; Kai-Yue Dong; Ke-Yu Chen; Wei Yao; Yao-Yao Lu; Jin-Luo Pang; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Phonon resonance enabled Cu(I) valence pinning in hydroxyapatite for photothermal CO2 hydrogenation - Wanguo Gao; Zhe Lu; Yecheng Leng; Chengyang Wu; Yingfang Yao; Xi Zhu; Junchuan Sun; Xiwen Yu; Cheng Wang; Congping Wu; Wenlei Wu; Bing Wang; et al. (Science Bulletin, 2025)

Uncertainty analysis of wave loads for multi-connected domain large floating bodies near islands and reefs - Xi-zhao Wang; Xue-kang Gu; Jun Ding; Qi-bin Wang; Zhi-wen Cai; Xiao-ming Cheng; C. Guedes Soares (Ocean Engineering, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Quinone-based electron shuttle boosts cytochrome synthesis and EPS production, improving anammox performance under Cr(VI) inhibition - Jingyu Liu; Lushan Li; Siyuan Cheng; Zhou Zhang; Yaozong Chen; Xi Tang; Chong-Jian Tang (Journal of Water Process Engineering, 2025)

Global, regional and national burden of lung cancer attributable to PM2.5 air pollution: Trends from 1990 to 2021 with projections to 2045 - Yingfan Deng; Zengbin Li; Pan Zhang; Yang Yang; Yuhan Xie; Yutong Cheng; Shuiyan Yu; Guixian Zhu; Lili Han; Lijun Jia; Wentao Xi; Pei Wang; et al. (Journal of Environmental Management, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

Machine learning-based detection of dynamic changes in mangrove forest, Beilun Estuary - Chuqi Long; Zhijun Dai; Xuefei Mei; Xixing Liang; Xuewei Zhang; Yangyang Xi; Riming Wang; Nguyen An Binh; Cong Mai Van; Jinping Cheng (Ocean & Coastal Management, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Tiered ecological risk assessment of perfluoroalkyl acid mixtures based on relative potency factor and species sensitivity distribution - Jianming Jiang; Xun Wang; Xi-Long Zhang; Hui Liu; Wen-Jun Hong; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Wei Luo (Environmental Geochemistry and Health, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Exogenous application of artificial humic substance can improve black soil properties and rice yield - Yue YUAN; Qingyu LIU; Shun ZHANG; Zhuqing LIU; Xi ZHANG; Kui CHENG; Fan YANG (Pedosphere, 2025)

Capillarity effect on groundwater dynamics during periodic forcing - Dawei Cheng; Hongbin Zhan; Xi Chen; Shengke Yang; Dongyong Sun; Xiuyu Liang (Journal of Hydrology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Reintegrating human excreta into the agriculture of rural China: Ecological risks and application strategies - Tianxin Li; Xi Chen; Rui Weng; Musa Manga; Shikun Cheng (Journal of Hazardous Materials, 2025)

Machine learning-aided model for predicting oily sludge pyrolysis under various feedstock and operating conditions - Cheng Lu; Dixuan Li; Beidou Xi; Guangji Hu; Jianbing Li (Journal of Hazardous Materials, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Unlocking the functional potential of porcine hemoglobin: An enzymatic hydrolysis-phosphorylation synergistic modification to enhance minced pork quality - Lili Liu; Jingyao Duan; Xi Zhang; Kenan Su; Yuhan Duan; Weiwei Cheng; Xinshuai Zhang (Food Bioscience, 2025)

Systematic assessments of ecological and health risks of soil pesticide residues - Tao Tang; Chaotang Lei; Lu Lv; Feidi Wang; Xi Cheng; Mingyu Gao; Jiajie Lou; Yuke Zhu; Nuohan Xu; Qi Zhang; Tao Lu; Haifeng Qian (Environmental Pollution, 2025)

Parametric study on hysteretic performance of separately-anchored self-centering concrete connections - Lu-Xi Li; Chao Li; Jin-Cheng Wu; Hong Hao (Engineering Structures, 2025)

Oriented conversion of low-value heavy oil to acetylene and hydrogen using pulsed spark discharge - Hang Wang; Rui Wu; Liguang Dou; Dengke Xi; Bangdou Huang; Zhuofei Wang; Shuai Zhang; Zhe Fan; Shuai Yang; Cheng Zhang; Guoxing Chen; Tao Shao (Chemical Engineering Journal, 2025)

Subducted sediment recycling and fractional crystallization of the Toba volcanic system constrained by plagioclase geochemistry - Meng-Hao Gao; Ping-Ping Liu; Dian-Bing Wang; Xi-Jun Liu; Gui-Bin Zhang; Cheng Xu (Chemical Geology, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Design of a Private Cloud Platform for Distributed Logging Big Data Based on a Unified Learning Model of Physics and Data - Xi Cheng; Haicheng Fu; Tursyngazy Mahabbat (Applied Geophysics, 2025)

Arsenic species and their health risks in intertidal macroalgae in response to seasonal variations - Yimei Xi; Hanyu Sun; Xiangfeng Zeng; Xinjie Wang; Cheng Li; Zhangxun Huang; Miao Yang; Long Wu (Marine Pollution Bulletin, 2025)

The convergence of food science and nutrigenomics: Exploring new frontiers in innovation and development opportunities - Junli Feng; Yu Zhang; Fuguang Zheng; Keyun Cheng; Xixi Zeng; Miaoyu Li; Chunlai Zeng; Xi Chen; Qing Shen (Trends in Food Science & Technology, 2025)

Imaging brain white matter function using resting-state functional MRI - Gong-Jun Ji; Zaixu Cui; Ryan C.N. D’Arcy; Wei Liao; Bharat B. Biswal; Qing Zhang; Cheng Luo; Yu-Feng Zang; Zhaohua Ding; Xi-Nian Zuo; John C. Gore; Kai Wang (Science Bulletin, 2025)

Functional lipid diversity and novel oxylipin identification for interspecies differentiation and nutritional assessment of commercial seahorse (Hippocampus) using untargeted and targeted lipidomics - Lijun Ge; Weibo Lu; Huixiang Wu; Jingjing Liang; Jie Liao; Keyun Cheng; Xi-xi Zeng; Si-wei Wang; Zejun Wang; Peiqing Mao; Zhujun Mao; Jing Xue; et al. (Food Chemistry, 2025)

Cross-linked nanosheets constructed as selective layers for the preparation of polyphenylene sulfide loose nanofiltration membranes for efficient separation of dyes and salts - Maliang Zhang; Huixin Lu; Yongyang Yin; Xiaotian Wang; Xi Du; Zhenhuan Li; Bowen Cheng (Desalination, 2025)

Lithospheric architecture and evolution of the Qinling Orogen of Central China and associated controls on metallogeny - Deng-Yang He; Kun-Feng Qiu; Hao-Cheng Yu; Simon M. Jowitt; Xi Zheng; Rajat Mazumder; Jun Deng (Earth-Science Reviews, 2025)

Thoracic perfusion of Esculentoside A-loaded thermosensitive hydrogel for the treatment of malignant pleural effusion in lung cancer - Jia You; Kun Shi; Xi Yang; Huawei Li; Lingnan Zheng; Yuanfeng Wei; JingYi Xu; Yue Li; Zhiyong Qian; Cheng Yi (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Chromosomal structural variation loci HSS1 and HSS6 lead to hybrid sterility in rice - Siqi Cheng; Zhenwei Xie; Hao Yu; Chaolong Wang; Xiaowen Yu; Jian Wang; Hai Zheng; Jiayu Lu; Xiaodong He; Keyi Chen; Junwen Gao; Yang Hu; et al. (Theoretical and Applied Genetics, 2025)

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Practice of multiple risk operation in multi-objective optimal operation of cascade hydropower plants: A case in lower branch of Lancang River Basin - Lianpeng Zhang; Shuaikang Yang; Chi Yuan; Hongxue Zhang; Jianxia Chang; Piao Xu; Jiajia Liu; Junyin Hu; Zhenxiang Xing; Cheng Wang; Xi Zhang (Journal of Hydrology, 2025)

Quorum sensing-enhanced electron transfer in anammox consortia: A mechanism for improved resistance to variable-valence heavy metals - Caiyan Qu; Jiong Tang; Jingyu Liu; Wenming Wang; Fengming Song; Siyuan Cheng; Xi Tang; Chong-Jian Tang (Journal of Hazardous Materials, 2025)

Nonlinear feedback of Asian summer monsoon to abrupt events in North Atlantic: Evidence from a precisely dated speleothem record during late MIS3 - Xi Chen; Jingyao Zhao; Kexin Wang; Xiyu Dong; Jiahui Cui; Liangkang Pan; Carlos Pérez-Mejías; Hai Cheng (Global and Planetary Change, 2025)

Dissolved oxygen prediction in the Dianchi River basin with explainable artificial intelligence based on physical prior knowledge - Junhao Wu; Xi Chen; Jinghan Dong; Nen Tan; Xiaoping Liu; Antonis Chatzipavlis; Philip LH. Yu; Adonis Velegrakis; Yining Wang; Yonggui Huang; Heqin Cheng; Diankai Wang (Environmental Modelling & Software, 2025)

The interfacial association dehydrogenation mechanism guides the design of anode Pt-Based catalysts for direct ammonia fuel cells: A perspective - Weidong Tang; Xiaohui Xu; Yu Cheng; Baocong Guo; Chenglin Yan; Peng Zhu; Xi Zhou; Tao Qian (Chemical Engineering Journal, 2025)

Bio-inspired multifunctional flexible visual sensors based on structural color materials - Long Bai; Yong Jin; Liangjie Shi; Xi Xia; Yue Wang; Cheng Hu; Yunbing Wang (Chemical Engineering Journal, 2025)

Dysregulation of Iron Homeostasis Mediated by FTH Increases Ferroptosis Sensitivity in TP53-Mutant Glioblastoma - Xuejie Huan; Jiangang Li; Zhaobin Chu; Hongliang Zhang; Lei Cheng; Peng Lun; Xixun Du; Xi Chen; Qian Jiao; Hong Jiang (Neuroscience Bulletin, 2025)

Analysis of co-seismic ionospheric disturbance of the Qinghai Mw 7.4 earthquake on May 21, 2021 - Qingshan Ruan; Hang Liu; Xitun Yuan; Shuyao Ge; Xi Cheng; Wu Wang (International Journal of Remote Sensing, 2025)

A multi-level monitoring mechanism for inland ships sewage based on software-defined cloud-edge-end collaborative architecture - Dong Han; Hualong Chen; Yuanqiao Wen; Changshi Xiao; Xiaodong Cheng; Xi Huang (Ocean & Coastal Management, 2025)

Mechanism and algorithm for addressing the impact of multiple scattering on surface elevation extraction in photon-counting LiDAR data - Zijia Wang; Sheng Nie; Xuebo Yang; Cheng Wang; Xiaohuan Xi; Xiaoxiao Zhu; Bisheng Yang (Remote Sensing of Environment, 2025)

Genomic analysis of Marinobacter sp. M5B reveals its role in alginate biosynthesis - Xiaoyu Si; Zhenhai Liu; Shuxin Cheng; Jingyao Xi; Bingrui Zeng; Meihui Li; Liping Zhu; Shigan Yan; Nan Zhang (Marine Genomics, 2025)

High-efficiency flavonoid deglycosylation of whole cells with surface display of α-L-rhamnosidase in Escherichia coli - Cheng-Hai Yan; Ding Wang; Ruo-Xi Mei; Lu Tan; Yi-Jiang-Cheng Li; Richard Ansah Herman; Yan Xu; Lu-Chan Gong; Jun Wang (Food Bioscience, 2025)

The role of GSK3β signaling mediated lysosomal biosynthesis dysregulation in fluoride-induced neurological impairment - Yi Cheng; Yuhui Du; Yue Hu; Xinying Wang; Qingyuan Li; Xi Yan; Ming Dou; Weihua Jia; Fangfang Yu; Yue Ba; Guoyu Zhou (Food and Chemical Toxicology, 2025)

A β-cyclodextrin-based supramolecular photonic crystal hydrogel biosensor with macroporous structures for naked-eye visual detection of cholesterol - Xi Wang; Jingjing Mu; Junjie Ren; Hairong Yu; Xingbin Lv; Ting Liang; Changjing Cheng (Carbohydrate Polymers, 2025)

Simultaneous nitrogen removal and phosphorus recovery in granular sludge-based partial denitrification/anammox-hydroxyapatite precipitation (PD/A-HAP) process under low C/N ratio and dissolved oxygen limitation - Lijie Chen; Zhenjun Wu; Jiayu Niu; Yihan Wang; Ming Cai; Jiale Xi; Yanlei Cui; Lang Cheng; Xinyi Fan (Bioresource Technology, 2025)

Dysregulation of Serum Exosomal Lipid Metabolism in Schizophrenia: A Biomarker Perspective - Chen-Xi Xu; Wei Huang; Xiao-Jie Shi; Yang Du; Jia-Quan Liang; Xuan Fang; He-Yuan Chen; Yong Cheng (Molecular Neurobiology, 2025)

CircXPO6 promotes breast cancer progression through competitively inhibiting the ubiquitination degradation of c-Myc - Aiqi Xu; Xi Li; Qiaoting Cai; Ciqiu Yang; Mei Yang; Hongfei Gao; Minyi Cheng; Xianzhe Chen; Fei Ji; Hailin Tang; Kun Wang (Molecular and Cellular Biochemistry, 2025)

Comprehensive LiDAR simulation with efficient physically-based DART-Lux model (II): Validation with GEDI and ICESat-2 measurements at natural and urban landscapes - Xuebo Yang; Cheng Wang; Tiangang Yin; Yingjie Wang; Dong Li; Nicolas Lauret; Xiaohuan Xi; Hongtao Wang; Ran Wang; Yantian Wang; Jean Philippe Gastellu-Etchegorry (Remote Sensing of Environment, 2025)

Accident analysis of waterway dangerous goods transport: Building an evolution network with text knowledge extraction - Xi Huang; Yuanqiao Wen; Fan Zhang; Haobin Li; Zhongyi Sui; Xiaodong Cheng (Ocean Engineering, 2025)

Preparation of composite film with CoFe2O4/MXene/chitosan for extending the shelf life of Kyoho grapes - Shujuan Chen; Xuanhao Zhou; Shuhan Yang; Xi Cheng; Wenjing Wang; Likou Zou; Shuliang Liu; Yong Yang; Aiping Liu; Li He (Food Bioscience, 2025)

Toxicity and intergenerational accumulation effect of tire wear particles and their leachate on Brachionus plicatilis - Hairong Lian; Lingyun Zhu; Chunwang Zha; Meng Li; Sen Feng; Fan Gao; Xin Zhang; Yilong Xi; Xinfeng Cheng; Xianling Xiang (Environmental Pollution, 2025)

Synthesis, molecular docking studies of formononetin derivatives as potent Bax agonists for anticancer activity - Wei-Dong Jia; Xue Bai; Qian-Qian Ma; Ming Bian; Chun-Mei Bai; Di Li; Li-Fei Li; Cheng-xi Wei; Li-Jun Yu (Natural Product Research, 2025)

Petrogenesis of the Dengying Formation Dolomite in Northeast Sichuan Basin, SW China: Constraints from Carbon-Oxygen Isotopic and Trace Elemental Data - Yuan He; Wenqi Li; Huichuan Liu; Nansheng Qiu; Kunyu Li; Cheng Xi; Xiaoliang Bai; Hongyu Long; Youlian Chen (Journal of Earth Science, 2025)

Serologic diagnosis of Entamoeba histolytica infection based on the gradient-based digital immunoassay - Wenwen Jing; Chuncao Liu; Chao Chen; Xi Chen; Jiaqi Wang; Meng Feng; Guodong Sui; Xunjia Cheng (Analytica Chimica Acta, 2025)

The nexus between aeration intensity and organic carbon capture in contact-stabilization process: Insights from molecular structure transition of dissolved organic matters - Shi-Xu Wang; Wei Yao; Chao-Xi Yang; Wen-Long He; Jing Li; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Challenges of quaternary ammonium antimicrobial agents: Mechanisms, resistance, persistence and impacts on the microecology - Jiaxin Zhang; Lei Cheng; Hao Li; Xi Chen; Lin Zhang; Tiantian Shan; Jiannan Wang; Ding Chen; Jiawei Shen; Xinxuan Zhou; Lichen Gou; Lixin Zhang; et al. (Science of The Total Environment, 2025)

Assessing lead fraction derived from passive microwave images and improving estimates at pixel-wise level - Xi Zhao; Jiaxing Gong; Meng Qu; Lijuan Song; Xiao Cheng (Remote Sensing of Environment, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Absorption, transportation, residual distribution of chiral 14C-dufulin in garlics and metabolism of its racemate - Ruonan Zheng; Binjie Wang; Jiye Wang; Xi Cheng; Qingfu Ye (Food Chemistry, 2025)

Trace alkali-assisted exfoliation of silk fibers into liquid crystalline mesogens: Phase behaviors and structural manipulation - Yongfeng Wang; Qingqing Cheng; Yiyao Chen; Lianhui Li; Shuqi Wang; Mingming Hao; Pei-Xi Wang; Ting Zhang (Chemical Engineering Journal, 2025)

Densely embedded homogeneous FeO nanoparticles in N-doped carbon frameworks: A 3D scaffold catalyst for high-temperature Fischer-Tropsch synthesis - Mengmeng Xi; Yang Cheng; Fanhui Meng; Xuefang Yao; Muhammad Asif Nawaz; Maria Saif; Zhong Li; Tomas Ramirez Reina (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Assessing thermal comfort for the elderly in historical districts and proposing adaptive urban design strategies: A case study in Zhenjiang, China - Yingnan Li; Yuhan Zhang; Yuedong Wang; Zipeng Song; Zhicheng Zhou; Lu Ding; Cen Chen; Xi Jin; Yuning Cheng (Landscape and Ecological Engineering, 2025)

Multi-well plate-based versatile platform for online fabricating alginate hydrogel microspheres and in-situ 3D cell culture - Ziwei Zhang; Longyu Chen; Hongliang Wang; Bo Tang; Yongqiang Cheng; Meijia Zhu; Xiaotong Li; Xiaoxiao Qi; Yifan Shao; Xi Zhang (Analytica Chimica Acta, 2025)

New dielectric-based smart sensor with multi-probe arrays for in-vivo monitoring of trunk water content distribution of a tree in a poplar stand - Xianglin Cheng; Xiaotong Wu; Yufan Zhu; Yang Zhao; Benye Xi; Xiaofei Yan; Ricardo F. de Oliveirad; Qiang Cheng (Computers and Electronics in Agriculture, 2024)

Supplementing ageing male laying breeders with lycopene alleviates oxidative stress in testis and improves testosterone secretion - Chun-Yu Ma; Ao-Chuan Yu; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xue-Ze Lv; Yong Guo; Cheng Long; Xiao-Long Qi (Theriogenology, 2024)

Deep reinforcement learning assisted memetic scheduling of drones for railway catenary deicing - Yu-Jun Zheng; Xi-Cheng Xie; Zhi-Yuan Zhang; Jin-Tang Shi (Swarm and Evolutionary Computation, 2024)

Molecular characterization of oxidized organic nitrogen in the polluted urban atmosphere of Beijing - Lei Liu; Junying Sun; Xiaojing Shen; Xi Cheng; Qi Chen; Quan Liu; Yangmei Zhang; Jing Zheng; Wei Wen; Xin Ma (Science of The Total Environment, 2024)

Butyl benzyl phthalate induces neurotoxicity in Eisenia fetida: Mechanisms revealed by biochemical and metabolomic analyses - Mengyao Yao; Cheng Zhang; Ying Xu; Zhengfu Yue; Mengyuan Pei; Wanjing Liu; Lanlan Zhang; Xi Chen; Shuhan Lei; Lusheng Zhu; Jun Wang; Peng Gao (Science of The Total Environment, 2024)

Aged rather than pristine polyvinyl chloride microplastic affect the development and structure of Vallisneria natans population - Xiaoqing Hu; Yuxuan Gao; Yi Cheng; Xi Li; Lei Wang; Xinhou Zhang; Guoxiang Wang (Science of The Total Environment, 2024)

Accident causation analysis of waterway dangerous goods transport: An approach based on improved ISM and graph theory - Xi Huang; Yuanqiao Wen; Fan Zhang; Zhongyi Sui; Xiaodong Cheng; Vedpal Arya (Ocean Engineering, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Fe-SMA for enhancing both structural robustness and seismic resilience: A pioneering study - Zhe-Xi Zhang; Cheng Fang; Michael C.H. Yam; Kwok-Fai Chung; Yue Zheng; Qun He (Engineering Structures, 2024)

Constructing multi-functional carbon-based aerogels for highly efficient photo-thermal desalination and water purification - Yuqian He; Linlin Yan; Mi Zhou; Kai Wang; Yingjie Zhang; Enrico Drioli; Jun Ma; Xi Quan Cheng (Desalination, 2024)

Effect of natural astaxanthin on sperm quality and mitochondrial function of breeder rooster semen cryopreservation - Jia-Yu Wu; Huan-Yu Kang; Yong Guo; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xue-Ze Lv; Cheng Long; Xiao-Long Qi (Cryobiology, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Incorporating embodied carbon transfer and sequestration service flows into regional carbon neutrality assessment in China - Henghui Xi; Xiaodan Liu; Xue Ding; Conghong Huang; Yu Tao; Qin Tao; Jiman Li; Xianbo Cheng; Fei Wang; Weixin Ou (Sustainable Production and Consumption, 2024)

Carbon-14 labeled transformation of atrazine in soils: Comparison of superabsorbent hydrogel coating and technical material - Xi Cheng; Jingying Yang; Chunrong Zhang; Tao Tang; Xueping Zhao; Qingfu Ye (Science of The Total Environment, 2024)

The viral trends and genotype diversity of norovirus in the wastewater of Shenzhen, China - Zhijiao Yue; Xiuyuan Shi; Hailong Zhang; Ziqi Wu; Chenxi Gao; Bincai Wei; Chen Du; Yuejing Peng; Xi Yang; Jing Lu; Yanpeng Cheng; Liping Zhou; et al. (Science of The Total Environment, 2024)

Research on ship navigation strategy in dynamic sea ice environments based on flexibility velocity obstacles algorithm - Bo Li; Jiaxing Gong; Xi Zhao; Xiao Cheng (Ocean Engineering, 2024)

Assessment of potentially toxic element contamination in commercially harvested invertebrates from the Beibu Gulf, China - Shuwen Zhao; Qiongyuan Su; Liangliang Huang; Caiguang Wang; jie Ma; Liang Zhu; Yanan Cheng; Xi Yang; Yiheng Yang; Bin Kang (Marine Environmental Research, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Can temperature be a low-cost tracer for modelling water age distributions in a karst catchment? - Zhicai Zhang; Xian Wang; Xi Chen; Yongyu Xie; Qinbo Cheng; Qing He; Tao Peng; Bo Chen; Chris Soulsby (Journal of Hydrology, 2024)

The effect of dual-frequency ultrasound on synergistic Sonochemical oxidation to degrade aflatoxin B1 - Hongchen Su; Yuxin Xie; Xi Cheng; Zhixuan Yang; Jin Mao; Hong Yang; Xiaoyun Xu; Siyi Pan; Hao Hu (Food Chemistry, 2024)

Impact of superabsorbent hydrogels on microbial community and atrazine fate in soils by 14C-labeling techniques - Xi Cheng; Jingying Yang; Tao Tang; Chunrong Zhang; Xueping Zhao; Qingfu Ye (Environmental Pollution, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Engineering sampling microneedles for biomolecules sensing - Yun Cheng; Xi Luan; Jiawu Weng; Lexiang Zhang; Fangfu Ye (Chemical Engineering Journal, 2024)

Study on mechanical properties and microcosmic morphology of polypropylene fiber reinforced recycled concrete after freeze–thaw cycles - Zhen-Jun He; Lu Zhang; Chuan Cheng; Ying Chen; Ying-Xi Jin (European Journal of Environmental and Civil Engineering, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Nicotinamide riboside activates SIRT3 to prevent paclitaxel-induced peripheral neuropathy - Xiaohan Sun; Weiting Huang; Dejin Yin; Xi Zhao; Xiaoling Cheng; Jin Zhang; Yue Hao (Toxicology and Applied Pharmacology, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Eco-friendly and highly efficient PM0.3 air filter made from nonwoven basalt fiber and electrospun nanocellulose fiber - Desalegn Atalie; Ze-Xin Chen; Hui Li; Cun-Guang Liang; Ming-Cheng Gao; Xiao-Xi Cheng; Peng-Cheng Ma (Journal of Hazardous Materials, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Injectable decellularized extracellular matrix hydrogel with cell-adaptable supramolecular network enhances cartilage regeneration by regulating inflammation and facilitating chondrogenesis - Wenli Dai; Xi Gong; Cheng Wang; Ping Liu; Weili Shi; Jin Cheng; Chenxi Cao; Xiaoqing Hu; Jianquan Wang; Yingfang Ao (Chemical Engineering Journal, 2024)

Enhanced broadband infrared radiation from rare earth orthochromites for High-Temperature radiative heat transfer - Zhi-Ling Xi; Xieeryazidan Aday; Meng Dong; Bao-Hua Liu; Cheng-Yu He; Guo-Yu Ren; Xiang-Hu Gao (Chemical Engineering Journal, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

A novel strategy with in vivo characterization, extraction, isolation and activity evaluation for discovery of absorbed anti-inflammatory oligosaccharides from Zhu-Ling decoction - Xi-yang Tang; Zhi-heng Shu; Peng-cheng Zhao; Wen Wei; Cai-lian Fan; Zhi-hong Yao; Xin-sheng Yao; Yi Dai (Carbohydrate Polymers, 2024)

Organophosphorus flame retardants in the Qiantang River of China: occurrence, source and ecological risk assessment - Wen-Jun Hong; Xi-Long Zhang; Hui Liu; Jian-Ming Jiang; Xun Wang; Minjie Li; Liang-Hong Guo; Cheng Ye; Hai-Gang Wu (Environmental Geochemistry and Health, 2024)

Distribution and biomagnification of Hexabromocyclododecanes (HBCDs) in edible marine fish in the Beibu Gulf, China: Implication for seafood dietary risk - Xi Yang; Liangliang Huang; Li Zhang; Liang Zhu; Yanan Cheng; Caiguang Wang; Bin Kang; Shuwen Zhao; Yiheng Yang (Marine Pollution Bulletin, 2024)

Fugacity- and biotransformation-based mechanistic insights into the trophic transfer of organophosphate flame retardants in a subtropical coastal food web from the Northern Beibu Gulf of China - Li Zhang; Xi Yang; Wee Vian Low; Jiaxin Ma; Cheng Yan; Zuhao Zhu; Lu Lu; Rui Hou (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Tempskya hailunensis sp. nov. (Tempskyaceae), a new tree fern with preserved leaf-like structures, from the Cretaceous of the Songliao Basin, Northeast China - Feng-Xiang Liu; Benjamin Bomfleur; Philipp Hiller; Xi Wang; Xiao-Nan Yang; Hai-E Du; Dong-Wei Wang; Yu-Jin Zhang; Ye-Ming Cheng (Review of Palaeobotany and Palynology, 2024)

Distinct influence of model electron shuttles on anaerobic mononitrophenols reduction in aquatic environments by Shewanella oneidensis MR-1 - Lisong Xia; Lei Cheng; Wenni Xi; Xiliang Zhang; Xianyang Shi (Journal of Hazardous Materials, 2024)

Modulate synthesis of CeMn solid solution using various alcohols for toluene catalytic oxidation: synergistic effect of Ce-Mn and reaction mechanism - Ye Jiang; Yinsheng Jiang; Siyuan Cheng; Yanyan Xi; Xin Sun; Yichao Xu; Zhengda Yang (Journal of Hazardous Materials, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Preparation and characterization of oregano essential oil microcapsules by gelatin/polysaccharide composite coagulation method - Kaiyue Wang; Yifan Wang; Xiumei Xi; Jinhang Lu; Yirong Wang; Peixin Zhao; Meng Cheng; Xiangyou Wang; Juan Wang (Food and Bioproducts Processing, 2024)

Development and validation of filtered drag models for fluidization of low-density Geldart A particles - Hairui Lin; Yuxi Si; Jianjian Dai; Zhuohan Li; Yan Liu; Lijun Wang; Xi Gao; Youwei Cheng (Chemical Engineering Journal, 2024)

Photothermal catalytic enhancement of lignocellulosic biomass conversion: A more efficient way to produce high-value products and fuels - Hui Wang; Xi Cheng; Zheng Li; Liquan Jing; Jinguang Hu (Chemical Engineering Journal, 2024)

Electrogenerated singlet oxygen and reactive chlorine species enhancing volatile fatty acids production from co-fermentation of waste activated sludge and food waste: The key role of metal oxide coated electrodes - Qingshan Lin; Shihao Xi; Boyi Cheng; Jinqi Jiang; Feixiang Zan; Yuanzhe Tang; Yeqing Li; Samir Kumar Khanal; Zongping Wang; Guanghao Chen; Gang Guo (Water Research, 2024)

High-molecular-weight dissolved organic matter enhanced phosphorus availability in paddy soils: Evidence from field and microcosm experiments - Hai-Bo Wang; Xi-Peng Liu; Bing-Jie Jin; Yu-Chen Shu; Cheng-Liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Soil and Tillage Research, 2024)

Mapping global mangrove canopy height by integrating Ice, Cloud, and Land Elevation Satellite-2 photon-counting LiDAR data with multi-source images - Jianan Yu; Sheng Nie; Wenjie Liu; Xiaoxiao Zhu; Zhongyi Sun; Jiatong Li; Cheng Wang; Xiaohuan Xi; Hongchao Fan (Science of The Total Environment, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Full-scale accelerated testing of geogrid-reinforced inverted pavements - Xi Jiang; Fengshou Zhang; Baoshan Huang; Hani Titi; Pawel Polaczyk; Yuetan Ma; Yanhai Wang; Zhiqiang Cheng (Geotextiles and Geomembranes, 2024)

Effects of polyphenols from walnut pellicle on the structure and allergenicity of walnut globulin - Jia-Hui Ma; Li-Qiu Ren; Tian-Xuan Tang; Yu-Yao Chen; Chen-Xi Zhang; Yu-Feng Ke; Yan Zhang; Mitchell N. Muskat; Xiang-Rong Cheng (Food Bioscience, 2024)

Fe/Co bimetallic nanozyme disrupting tumorous Self-Regulatory pathways to potentiate ferroptosis - Qing Liu; Qian Chen; Xi Deng; Yutong Zhu; Zhangpeng Shi; Runjie Miao; Ming Ma; Nian Ran; Cheng Li; Hangrong Chen (Chemical Engineering Journal, 2024)

Leaf area index estimation in maize and soybean using UAV LiDAR data - Shezhou Luo; Weiwei Liu; Qian Ren; Hanquan Wei; Cheng Wang; Xiaohuan Xi; Sheng Nie; Dong Li; Dan Ma; Guoqing Zhou (Precision Agriculture, 2024)

SfuPKS2, a novel type III polyketide synthase from Sargassum fusiforme, shows high substrate specificity - Jia-Min Xu; Yi-Cheng Xu; Chen-Xi Cheng; Dong-Sheng Zhao; Zhi-Wei Hu; Shu-Ming Li; Salah Fatouh Abou-Elwafa; Xiufeng Yan; Hui-Xi Zou; Nan Li (Journal of Applied Phycology, 2024)

Ethanol Treated Mn–Zr Compound for Fluoride Removal and its Adsorption Mechanism - Yuanyao Ye; Xueyi Yan; Xi Li; Shijing Huang; Wei Jiang; Dongqi Liu; Yongzheng Ren; Dongle Cheng (International Journal of Environmental Research, 2024)

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

A novel approach for estimating fractional cover of crops by correcting angular effect using radiative transfer models and UAV multi-angular spectral data - Yuanyuan Pan; Wenxuan Wu; Jiaoyang He; Jie Zhu; Xi Su; Wanyu Li; Dong Li; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Computers and Electronics in Agriculture, 2024)

Time-frequency analysis of nonlinear structures under nonstationary excitation by directly solving structural dynamic equation through absolute displacement - Xi-Mei Li; Ting-Long Zhao; Cheng Tao (Soil Dynamics and Earthquake Engineering, 2024)

Insulin resistance and its relationship with long-term exposure to ozone: Data based on a national population cohort - Zenglei Zhang; Cheng Luan; Chunqi Wang; Tiantian Li; Yi Wu; Xin Huang; Bolin Jin; Enming Zhang; Qiuhong Gong; Xianliang Zhou; Xi Li (Journal of Hazardous Materials, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

The Endometrial Stem/Progenitor Cells and Their Niches - Baolan Sun; Xi Cheng; Qiang Wu (Stem Cell Reviews and Reports, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Intra-annual vegetation changes and spatial variation in China over the past two decades based on remote sensing and time-series clustering - Xi Cheng; Mingliang Luo; Ke Chen; Jian Sun; Yong Wu (Environmental Monitoring and Assessment, 2024)

Determining the optimal thin layer height for single-station ionospheric modeling and its influence on the estimation of DCB - Hui Xi; Hu Jiang; Jiachun An; Na Cheng; Tianyang Bai; Jingxue Bi (GPS Solutions, 2024)

A graphene oxide-assisted protein immobilization paper-tip immunosensor with smartphone and naked eye readout for the detection of okadaic acid - Yifan Shao; Xiaotong Li; Xiaoxiao Qi; Juan Li; Sheng Zhao; Peiyan Sun; Hongliang Wang; Yongqiang Cheng; Ziwei Zhang; Longyu Chen; Xi Zhang; Meijia Zhu (Analytica Chimica Acta, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Intrinsically stretchable jellyfish-like gold nanowires film as multifunctional wearable chemical and physical sensors - Heng Zhang; Fenge Lin; Gangsheng Chen; Cheng Yang; Hanqiang Zhang; Mengwen Yan; Heng Li; Xi Wang; Wenlong Cheng; Yi Chen (Chemical Engineering Journal, 2024)

Flash spinning polyethylene/Fe3O4 magnetic drive fibers for oil absorption underwater - Dengkun Shu; Xingyu Long; Pengju Zhao; Lang Wang; Zhenhua Li; Chunzu Cheng; Shuo Yang; Long Jiao; Peng Xi; Lei Xia; Chenyang Li; Bowen Cheng (Chemical Engineering Journal, 2024)

Bright cyan emission from Eu-Doped borosilicate glasses by optimizing reduction of Eu3+ to Eu2+ in ambient atmosphere - Jiuzhi Cui; Yufeng Wen; Runchuan Chen; Xi Cheng; Meidong Yu; Jiandi Liu; Zuofu Hu; Jiajun He; Zhuohao Xiao; Xin-Yuan Sun (Chemical Engineering Journal, 2024)

Integration of lactic acid biorefinery with treatment of red mud from alumina refinery: win–win paradigm for waste valorization - Binyuan Gao; Xi Liu; Yudie Wu; Haina Cheng; Hongbo Zhou; Yuguang Wang; Zhu Chen (Bioresource Technology, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Investigation of Pore Structure and Adsorption/Desorption Properties of Coal in the Non-uniform Stress Zone: Implications for Coal and Gas Outburst - Zhuang Lu; Liang Wang; Songwei Wu; Peng Chu; Chuanpeng Xi; Hao Wang; Yuanping Cheng (Natural Resources Research, 2024)

Inhibition of Notch3/Hey1 ameliorates peribiliary hypoxia by preventing hypertrophic hepatic arteriopathy in biliary atresia progression - Xiaopan Chang; Shuiqing Chi; Xi Zhang; Xiangyang Li; Cheng Yu; Ying Zhou; Shaotao Tang (Histochemistry and Cell Biology, 2024)

Exosomes Derived from hucMSCs Primed with IFN-γ Suppress the NF-κB Signal Pathway in LPS-Induced ALI by Modulating the miR-199b-5p/AFTPH Axis - Chun Wang; Yiran Yang; Chen Jiang; Cheng Xi; Yunxiang Yin; Haiying Wu; Chuanyun Qian (Cell Biochemistry and Biophysics, 2024)

Identification of a Clinical Spirometra mansoni Plerocercoid Isolate Using Molecular and Morphological Data - Si Si Ru; Chi Cheng; Peng Jiang; Xi Zhang (Acta Parasitologica, 2024)

MitoQ protects against carbon tetrachloride-induced hepatocyte ferroptosis and acute liver injury by suppressing mtROS-mediated ACSL4 upregulation - Li Tao; Yu-Feng Xue; Fei-Fei Sun; Xue He; Hong-Qian Wang; Cheng-Cheng Tong; Cheng Zhang; De-Xiang Xu; Xi Chen (Toxicology and Applied Pharmacology, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Unlocking sustainable resource management: A comprehensive SWOT and thematic analysis of FinTech with a focus on mineral management - Mehrbakhsh Nilashi; Rabab Ali Abumalloh; Ooi Keng-Boon; Garry Wei-Han Tan; Tat-Huei Cham; Eugene Cheng-Xi Aw (Resources Policy, 2024)

Comparison of hexavalent chromium and cadmium removal from wastewater in constructed rapid infiltration system with layered double hydroxides (LDHs) modified maifanite substrates: Physical, chemical and microbial mechanism - Jingtian Gao; Xiangling Zhang; Jing Bai; Xuhao Li; Chen Wang; Jing Cheng; Zhouying Xu; Xi Jin (Journal of Water Process Engineering, 2024)

Fhb7-GST catalyzed glutathionylation effectively detoxifies the trichothecene family - Bingqian Hou; Dawei Wang; Fangfang Yan; Xinxin Cheng; Yongchang Xu; Xuepeng Xi; Wenyang Ge; Silong Sun; Peisen Su; Lanfei Zhao; Zhongfan Lyu; Yongchao Hao; et al. (Food Chemistry, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Is electric truck a viable alternative to diesel truck in long-haul operation? - Xi Cheng; Jane Lin (Transportation Research Part D: Transport and Environment, 2024)

A natural mutant kumquat fruit with abnormal oil glands shows lower volatile production, better fruit flavor and higher resistance to postharvest disease - Man Zhu; Yang Wang; Zhebin Zeng; Xi Wu; Jiacheng Teng; Jingzong Zhang; Qianrong Han; Qiaoli Ma; Chuanwu Chen; Yunjiang Cheng; Xiuxin Deng; Niels J. Nieuwenhuizen; et al. (Postharvest Biology and Technology, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

A novel framework for high resolution air quality index prediction with interpretable artificial intelligence and uncertainties estimation - Junhao Wu; Xi Chen; Rui Li; Anqi Wang; Shutong Huang; Qingli Li; Honggang Qi; Min Liu; Heqin Cheng; Zhaocai Wang (Journal of Environmental Management, 2024)

Enhancing the storage stability of mulberry anthocyanin extract through ternary complex with whey protein isolate and ferulic acid at neutral pH: Investigation of binding mechanisms - Yong Cheng; Xi Chen; Tian Yang; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Fang Qin; Jie Chen; Zhiyong He (Food Hydrocolloids, 2024)

Current-use pesticides monitoring and ecological risk assessment in vegetable soils at the provincial scale - Wei Zuo; Yang Zhao; Peipei Qi; Chunrong Zhang; Xueping Zhao; Shenggan Wu; Xuehua An; Xinju Liu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2024)

Dynamic in situ measurement of axial segregation of E-CAT particles in a bubbling fluidized bed - Biaosheng Luo; Baiyu Lu; Xi Gao; Cheng Li (Chemical Engineering Journal, 2024)

Teriflunomide Promotes Blood–Brain Barrier Integrity by Upregulating Claudin-1 via the Wnt/β-catenin Signaling Pathway in Multiple Sclerosis - Yipeng Zhao; Chen Chen; Xiuqing Xiao; Ling Fang; Xi Cheng; Yanyu Chang; Fuhua Peng; Jingqi Wang; Shishi Shen; Shilin Wu; Yiying Huang; Wei Cai; et al. (Molecular Neurobiology, 2024)

Xiashengella succiniciproducens gen. nov., sp. nov., a succinate-producing bacterium isolated from an anaerobic digestion tank in the family Marinilabiliaceae of the order Bacteroidales - Hao-Jie Huang; Xi Zhang; Xin-Wei Sun; Biao Chen; Xiu-Tong Li; Nan Zhou; Rashidin Abdugheni; Qiu-Yin Cheng; Tie-Jun Zhang; Yao Liu; Yong Jiang; Ye Deng; et al. (Archives of Microbiology, 2024)

Influence of calcium concentration on larval adhesion in a highly invasive fouling ascidian: From morphological changes to molecular mechanisms - Jiawei Cheng; Shiguo Li; Xi Li; Aibin Zhan (Marine Pollution Bulletin, 2024)

Unequal transfer and its policy implications of carbon emissions and economic benefits embodied among Central Plains urban agglomeration - Shuan Peng; Min Chen; Zefeng Qi; Nihed Benani; Tao Wang; Xuefang Wu; Xi Cheng; Jian Lin Chen; Guozhu Mao; Pingjian Yang (Urban Climate, 2024)

Modeling and assessing the impacts of climate change on groundwater recharge in endorheic basins of Northwest China - Wenju Cheng; Qi Feng; Haiyang Xi; Xinwei Yin; Lei Cheng; Celestin Sindikubwabo; Baiting Zhang; Yuqing Chen; Xinyue Zhao (Science of The Total Environment, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

A dolomite-based record of seawater calcium isotope composition over the Neogene - Xiao-Feng Liu; Xiao-Ming Liu; Shikui Zhai; Zhaofeng Zhang; Dongjie Bi; Xi-Kai Wang; Cheng Cao; Xinyu Liu (Geochimica et Cosmochimica Acta, 2024)

Enhancing phosphorus release from sewage sludge via anaerobic treatment: State-of-art progress and future challenges - Wei Yao; Chao-Xi Yang; Yan Lu; Yao-Yao Lu; Shi-Xu Wang; Bao-Cheng Huang; Ren-Cun Jin (Chemical Engineering Journal, 2024)

Engineering α-MoO3/TiO2 heterostructures derived from MOFs/MXene hybrids for high-performance triethylamine sensor - Weining Liu; Hairong Li; Dandan Huang; Xi Tan; Mingyang Zhao; Qionglin Cheng; Ming Yi; Qi Ding; Yaqian Ren; Guohan Liu (Chemical Engineering Journal, 2024)

Genetically predicted gut microbiome and risk of oral cancer - Kun Xiang; Cheng-Xi Li; Ran Chen; Chun-Hui Zhao (Cancer Causes & Control, 2024)

Brittleness ductility transition depth of new fracture in the Baodi Miaozhuang Uplift - He Li; Yi-Bing Dong; Yi-Xi Wang; Wu-Ping Gao; Cheng-Guo Yan; Ling-Ling Cai; Bo-Yang Wu; Peng Zhao (Applied Geophysics, 2024)

A novel visible-light-driven Z-scheme C3N5/BiVO4 heterostructure with enhanced photocatalytic degradation performance - Dongqi Ma; Wuyou Wang; Qinzheng Wang; Yelan Dai; Kai Zhu; Haocheng Xu; Cheng Yuan; Pengyu Dong; Xinguo Xi (Environmental Science and Pollution Research, 2024)

Efficient lithium recovery from electrolytic aluminum slag via an environmentally friendly process: Leaching behavior and mechanism - Li Cui; Weihong Wang; Xi Chao; Jianming Gao; Fangqin Cheng (Journal of Cleaner Production, 2024)

An improved re-entrant honeycomb with programmable densification and multistage energy-absorbing performance - Wei Zhong Jiang; Xing Chi Teng; Xi Hai Ni; Xue Gang Zhang; Xian Cheng; Wei Jiang; Dong Han; Yi Zhang; Xin Ren (Engineering Structures, 2024)

Advances in research on arboviral acquisition from hosts to mosquitoes - Yibin Zhu; Xi Yu; Liping Jiang; Yibaina Wang; Xiaolu Shi; Gong Cheng (Current Opinion in Insect Science, 2024)

Rapid and efficient preparation of cationized lignin for downstream high value-added utilization of biodegradable antimicrobial nanofibrous membranes - Yu-Fei Gao; Cheng-Ye Ma; Qian Sun; Xin-Xu Zhang; Jing Liu; Jia-Long Wen; Rou-Xi Chen; Hsing-Lin Wang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Highly efficient activation of periodate by a manganese-modified biochar to rapidly degrade methylene blue - Jiamin Gong; Honghui Jiang; Xiang Li; Hao Cheng; Ziqi Wang; Jingju Cai; Meifang Li; Ping Wang; Hui Wang; Xi Hu; Xinjiang Hu (Environmental Research, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Single-Cell Mapping of Brain Myeloid Cell Subsets Reveals Key Transcriptomic Changes Favoring Neuroplasticity after Ischemic Stroke - Fangxi Liu; Xi Cheng; Chuansheng Zhao; Xiaoqian Zhang; Chang Liu; Shanshan Zhong; Zhouyang Liu; Xinyu Lin; Wei Qiu; Xiuchun Zhang (Neuroscience Bulletin, 2024)

TREM-2 Drives Development of Multiple Sclerosis by Promoting Pathogenic Th17 Polarization - Siying Qu; Shengfeng Hu; Huiting Xu; Yongjian Wu; Siqi Ming; Xiaoxia Zhan; Cheng Wang; Xi Huang (Neuroscience Bulletin, 2024)

Short-Term Efficacy of Cerebello-spinal tDCS and Body Weight-Supported Treadmill Training in the Hypertrophic Olivary Degeneration: a Rare Case Report - Xi-Chen Wang; Nai-Qing Cai; Xiao-Ping Cheng; Lin Zhang; Wen-Zong Wang; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Inactivation of Staphylococcus aureus in water by dielectric barrier discharge plasma jet: The role of inorganic ions, organic matter, and turbidity - Zimu Xu; Yandan Tang; Shuheng Hu; Yan Lan; Wenhao Xi; Wei Han; Danzhou Wu; Fan Yang; Cheng Cheng (Journal of Water Process Engineering, 2023)

Efficient degradation of 2,4-dichlorophenol by heterogeneous electro-Fenton using bulk carbon aerogels modified in situ with FeCo-LDH as cathodes: Operational parameters and mechanism exploration - Cheng Xue; Jianrui Ma; Xi Chen; Dongfang Liu; Wenli Huang (Journal of Environmental Management, 2023)

Enrichment of resistant starch in starch-protein hydrolysate binary matrix by modulating pH during thermal processing - Cuihong Dai; Zihang Cheng; Yanyu Chen; Dongling Qiao; Gaolei Xi; Qiuling Wang; Fan Zhu; Siming Zhao; Binjia Zhang (Food Research International, 2023)

Coupled effects of temperature and relative humidity on desiccation curling of a clayey soil - Zhan-Ming Yang; Qing Cheng; Chao-Sheng Tang; Ben-Gang Tian; Xi-Ying Zhang (Engineering Geology, 2023)

Constructing triple-network cellulose nanofiber hydrogels with excellent strength, toughness and conductivity for real-time monitoring of human movements - Jianming Wu; Qian Ma; Qingkai Pang; Shuaishuai Hu; Zhihao Wan; Xiangfang Peng; Xi Cheng; Lihong Geng (Carbohydrate Polymers, 2023)

Mixotrophic culture of Chaetoceros sp. and the synergistic carbon and energy metabolism - Shengzhou Shan; Shanshan Wang; Xi Yan; Kang Chen; Li Liang; Xiaohui Li; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Isolation, identification and characterization of Aeromonas allosaccharophila from infected farmed leech (Whitmania pigra) in Jiangsu, China - Gui-Yan Shao; Su-Yan Wang; Xue-Shuang Jiang; Qing-Qing Tian; Yu-Xi Lu; Bo-Xing Cheng; Fei Liu (Aquaculture, 2023)

Zircon U–Pb geochronology, Hf–O isotopes and whole-rock geochemistry of A-type granitoids in Halajun, South Tienshan, NW China: Implications for subdivision, petrogenesis and tectonic settings - Tian-Chu Chen; Ming-Xing Ling; Yu-Long Liu; Ying Wei; Xi-Hui Cheng; Xiao-Yan Jiang; Shuo Xue; Ze-Bin Luo; Jiang-Hao Bai (Lithos, 2023)

Sustainable application of coal fly ash: One-step hydrothermal cleaner production of silicon-potassium mineral fertilizer synergistic alumina extraction - Xi Chao; Ting-an Zhang; Guozhi Lv; Qiuyue Zhao; Fangqin Cheng; Yanxia Guo (Journal of Cleaner Production, 2023)

Identifying the impacts of land use landscape pattern and climate changes on streamflow from past to future - Yingshuo Lyu; Hong Chen; Zhe Cheng; Yuetong He; Xi Zheng (Journal of Environmental Management, 2023)

Effects of whey protein isolate and ferulic acid/phloridzin/naringin/cysteine on the thermal stability of mulberry anthocyanin extract at neutral pH - Yong Cheng; Xi Chen; Tian Yang; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Fang Qin; Jie Chen; Zhiyong He (Food Chemistry, 2023)

Bacterial distinctions in practical rural sewage collection systems caused by the location, season, and system type - Wenkai Li; Tianlong Zheng; Ke Feng; Yingqun Ma; Jianguo Liu; Wei Xu; Wenhu Cheng; Xiaopeng Xi; Jianrong Luo (Environmental Research, 2023)

Unraveling the crucial role of Mo2N from Fe/Mo bimetal MOF-derived catalyst in initiating Fe3+/Fe2+ redox cycle to activate peroxymonosulfate for dibutyl phthalate degradation - Xi Chen; Yunfeng Chen; Songrong Li; Cheng Xue; Dongfang Liu; Wenli Huang (Chemical Engineering Journal, 2023)

One-pot conversion of cellulose to HMF under mild conditions through decrystallization and dehydration in dimethyl sulfoxide/tetraethylammonium chloride - Qinrui Du; Xusheng Guo; Haoxiang Zhu; Youwei Cheng; Lijun Wang; Xi Li (Chemical Engineering Journal, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

The Association Between Serum Magnesium Levels and Gestational Diabetes Mellitus: a Systematic Review and Meta-Analysis - Qian Ren; Hongya Wang; Yan Zeng; Xiaozhen Tan; Xi Cheng; Tingting Zhou; Wei Huang; Yong Xu (Biological Trace Element Research, 2023)

Butachlor (BTR) degradation by dielectric barrier discharge plasma in soil: Affecting factors, degradation route, and toxicity assessment - Shuheng Hu; Xin Jin; Xueyan Chen; Bin Lv; Wenhao Xi; Yan Lan; Wei Han; Zimu Xu; Cheng Cheng (Chemosphere, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

α-Linolenic acid-regulated testosterone biosynthesis via activation of the JNK-SF-1 signaling pathway in primary rooster Leydig cells - Zhi-Xian Zhao; Ming-Yu Shang; Cheng Long; Xue-Jun Yao; Xiao-Bo Gao; Yong Guo; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xiao-Long Qi (Theriogenology, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Spatiotemporal variability and controlling factors of groundwater depletion in endorheic basins of Northwest China - Wenju Cheng; Qi Feng; Haiyang Xi; Xinwei Yin; Celestin Sindikubwabo; Telesphore Habiyakare; Yuqing Chen; Xinyue Zhao (Journal of Environmental Management, 2023)

Synthesis of artificial humic acid-urea complex improves nitrogen utilization - Yongxu Jin; Xi Zhang; Yue Yuan; Yibo Lan; Kui Cheng; Fan Yang (Journal of Environmental Management, 2023)

Effects of carbon to nitrogen ratio on oxygen mass transfer characteristics in wastewater and biofilms - Jiehui Ren; Xiaoxin Yang; Jiayao Xi; Wen Cheng (Journal of Environmental Chemical Engineering, 2023)

Determination of heat transfer representative element volume and three-dimensional thermal conductivity tensor of fractured rock masses - Zheng-Wei Li; Chuan-Yuan Huang; Hai-Xi Wang; Shi-Cheng Xing; Meng-Cheng Long; Yuan Liu (International Journal of Rock Mechanics and Mining Sciences, 2023)

Bioleaching of ion-adsorption rare earth ores by biogenic lixiviants derived from agriculture waste via a cell-free cascade enzymatic process - Binyuan Gao; Min Gan; Chongran Sun; Hui Chen; Xi Liu; Qianzi Liu; Yuguang Wang; Haina Cheng; Hongbo Zhou; Zhu Chen (Hydrometallurgy, 2023)

Effects of different storage containers on the flavor characteristics of Jiangxiangxing baijiu - Lulu Wei; Jianfeng Hu; Chengkang Pan; Pingyan Cheng; Jian Zhang; Dezhou Xi; Mingxue Chen; Lunwei Lu; Hu Lu; Feng Hu (Food Research International, 2023)

Preparation and characterization of inclusion complex of Myristica fragrans Houtt. (nutmeg) essential oil with 2-hydroxypropyl-β-cyclodextrin - Xiaohui Xi; Jialing Huang; Shengyang Zhang; Qian Lu; Zhengfeng Fang; Cheng Li; Qing Zhang; Yuntao Liu; Hong Chen; Aiping Liu; Shuxiang Liu; Caixia Wang; et al. (Food Chemistry, 2023)

Storage stability and multi-spectroscopy analysis of the ternary complex induced by mulberry anthocyanin extract interacting with whey protein isolate and rutin under acidic conditions - Yong Cheng; Xi Chen; Tian Yang; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Fang Qin; Jie Chen; Zhiyong He (Food Hydrocolloids, 2023)

Quantitative examination of microstructural transformations of clay-rich sediments in river-dominated deltas under the influence of polluted pore water - Xiong-Ying Ma; Zhan Liu; Zhao Xia; Chen-Xi Su; Yin Cheng; Hao Yu; Xin Kang (Environmental Pollution, 2023)

Surrogate modeling and global sensitivity analysis for the simultaneous growth of multiple hydraulic fractures - Shaoyi Cheng; Bisheng Wu; Ming Zhang; Xi Zhang; Yanhui Han; Robert G. Jeffrey (Computers and Geotechnics, 2023)

Study on the effective removal of chlorpyrifos from water by dielectric barrier discharge (DBD) plasma: The influence of reactive species and different water components - Zimu Xu; Xueyan Chen; Xin Jin; Shuheng Hu; Yan Lan; Wenhao Xi; Wei Han; Cheng Cheng (Chemical Engineering Journal, 2023)

Identification of Fluid Interference in Coalbed Methane Co-production Based on Produced Water: A Case Study in the Hancheng Block, Southeastern Ordos Basin, North China - Chen Guo; Xi Cheng; Jiang Gou; Junzhe Gao; Reza Taherdangkoo; Jinxiao Yang; Lingling Lu (Natural Resources Research, 2023)

The Mitochondrial-Derived Peptide (MOTS-c) Interacted with Nrf2 to Defend the Antioxidant System to Protect Dopaminergic Neurons Against Rotenone Exposure - Jingsong Xiao; Qifu Zhang; Yaohui Shan; Feng Ye; Xi Zhang; Jin Cheng; Xiaogang Wang; Yuanpeng Zhao; Guorong Dan; Mingliang Chen; Yan Sai (Molecular Neurobiology, 2023)

Earthworms enhance the inhibition efficiency of 3,4-dimethylpyrazole phosphate on soil nitrification by altering soil AOB communities and gut denitrifier communities - Bing-Jie Jin; Xi-Peng Liu; Miao Zhang; Yan Hu; Cheng-Liang Sun; Gang Li; Yong-Guan Zhu; Xian-Yong Lin (Biology and Fertility of Soils, 2023)

Development and analysis of a universal label-free micro/nano component for three-channel detection of silver ions, mercury ions, and tetracycline - Luhui Wang; Mengyang Hu; Rong Liu; Sunfan Xi; Meng Cheng; Yangyinchun Bao; Na Wang; Yafei Dong (Analytica Chimica Acta, 2023)

Late Carboniferous bimodal volcanic rocks of the West Junggar Terrane, NW China: Implications for the postcollisional tectonic setting of the southwestern CAOB - Xi Wang; Ran Wang; Pan Qu; Sanyou Cheng; Yonghui Xin (International Geology Review, 2023)

Assessment of 13 essential and toxic trace elements in tumor and peritumoral brain tissues from human glioblastoma - Hao-Long Zeng; Binmei Jia; Qing Yang; Fengbo Zeng; Huijun Li; Chao-Xi Li; Liming Cheng (JBIC Journal of Biological Inorganic Chemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Papermaking wastewater treatment coupled to 2,3-butanediol production by engineered psychrotrophic Raoultella terrigena - Wang Yue; Yang Genji; Wu Bowen; Mi Yaozu; Zhou Yang; Ma Tian; Zang Hailian; Xi Chuanwu; Cheng Yi; Li Chunyan (Journal of Hazardous Materials, 2023)

Does environmental information disclosure affect corporate cash flow? An analysis by taking media attentions into consideration - Xi Cheng; Chao Feng (Journal of Environmental Management, 2023)

Spatio-temporal distribution of organochlorine pesticides in agricultural soils of southeast China during 2014-2019 - Wei Zuo; Qin Lin; Xinju Liu; Lu Lv; Chunrong Zhang; Shenggan Wu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2023)

Interpretation and explanation of convolutional neural network-based fault diagnosis model at the feature-level for building energy systems - Guannan Li; Liang Chen; Cheng Fan; Tao Li; Chengliang Xu; Xi Fang (Energy and Buildings, 2023)

A one- and three-dimensional coupled model and simulation investigation for the large-scale oil-heating type Mg-based hydrogen storage tank - Xi Lin; Cheng-long Yin; Li Ren; Yinghui Li; Zi Li; Qiuyu Zhang; Zhigang Hu; Jianxin Zou (Chemical Engineering Journal, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Food flavor analysis 4.0: A cross-domain application of machine learning - Xiangquan Zeng; Rui Cao; Yu Xi; Xuejie Li; Meihong Yu; Jingling Zhao; Jieyi Cheng; Jian Li (Trends in Food Science & Technology, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

Mineral-induced catalytic mechanism of sodium-calcium binary catalyst during coal char gasification - Junqin Yu; Lu Ding; Chinnathan Areeprasert; Longkang Xi; Chen Cheng; Jiajian Wang; Guangsuo Yu (Journal of Cleaner Production, 2023)

A molecular investigation on the effects of OMEX addition on soot inception of diesel pyrolysis - Zhihao Xing; Mengwei Yu; Cheng Chen; Xi Jiang (Fuel, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Grain yield prediction using multi-temporal UAV-based multispectral vegetation indices and endmember abundance in rice - Xi Su; Jiacheng Wang; Lu Ding; Jingshan Lu; Jiawen Zhang; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Field Crops Research, 2023)

Simultaneous removal of antibiotic-resistant Escherichia coli and its resistance genes by dielectric barrier discharge plasma - Shuheng Hu; Yuhang Fu; Muen Xue; Yan Lan; Wenhao Xi; Zimu Xu; Wei Han; Danzhou Wu; Cheng Cheng (Environmental Research, 2023)

Aromatic disulfide-induced self-reinforcing polyurethane elastomer with self-healability - Yanlong Luo; Jialiang Chen; Gaohua Situ; Chichao Li; Chenrui Zhang; Fanzhu Li; Cheng-Hui Li; Zhenyang Luo; Xi Zhang (Chemical Engineering Journal, 2023)

Artifacts in High-Frequency Passive Surface Wave Dispersion Imaging: Toward the Linear Receiver Array - Feng Cheng; Jianghai Xia; Chaoqiang Xi (Surveys in Geophysics, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Targeting Peripheral μ-opioid Receptors or μ-opioid Receptor-Expressing Neurons Does not Prevent Morphine-induced Mechanical Allodynia and Anti-allodynic Tolerance - Feng Du; Guangjuan Yin; Lei Han; Xi Liu; Dong Dong; Kaifang Duan; Jiantao Huo; Yanyan Sun; Longzhen Cheng (Neuroscience Bulletin, 2023)

Umbelliferon: a review of its pharmacology, toxicity and pharmacokinetics - Zhi Lin; Xi Cheng; Hui Zheng (Inflammopharmacology, 2023)

Comparative analysis of the gut microbiota of wild wintering whooper swans (Cygnus Cygnus), captive black swans (Cygnus Atratus), and mute swans (Cygnus Olor) in Sanmenxia Swan National Wetland Park of China - Jun-Xian Mi; Kai-Li Liu; Wen-Li Ding; Ming-Hui Zhang; Xue-Fei Wang; Aftab Shaukat; Mujeeb Ur Rehman; Xi-Lan Jiao; Shu-Cheng Huang (Environmental Science and Pollution Research, 2023)

DFT-based analysis of siderophore-metal ion interaction for efficient heavy metal remediation - Yi-Cheng Xu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Environmental Science and Pollution Research, 2023)

Nonenantioselective environmental behavior of a chiral antiviral pesticide dufulin in aerobic soils - Weiwei Zhang; Xin Zhou; Qingfu Ye; Xi Cheng; Sufen Zhang; Zhiyang Yu; Wei Wang (Science of The Total Environment, 2023)

Molecular detection and genetic characteristics of a novel porcine circovirus (porcine circovirus 4) and porcine reproductive and respiratory syndrome virus in Shaanxi and Henan Provinces of China - Xi-Meng Chen; You-Yi Zhao; Xiao-Chen Liu; Ying-Ying Han; Yuan-Hang Zhang; Cheng-Yao Hou; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Assessing the impacts of natural conditions and human activities on terrestrial water storage in Loess Plateau, China - Cheng-xi Wang; Jian-wu Yan; Wei Liang; Shao-bo Sun; Fen Gou; Xiao-fei Li; Yuan-yuan Luo; Feng-jiao Wang (Journal of Mountain Science, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Fate characteristics of the chiral pesticide dufulin in flooded anaerobic soils and its interaction with soil microorganisms - Xin Zhou; Weiwei Zhang; Siyao Shao; Sufen Zhang; Xi Cheng; Qingfu Ye (Science of The Total Environment, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Artificial humic acid promotes growth of maize seedling under alkali conditions - Fan Yang; Yue Yuan; Qingyu Liu; Xi Zhang; Shuang Gai; Yongxu Jin; Kui Cheng (Environmental Pollution, 2023)

Design of hybrid g-C3N4/GO/MCE photocatalytic membranes with enhanced separation performance under visible-light irradiation - Junyang Pan; Dan Hua; Yiping Hong; Xi Cheng; Fangsong Guo; Kok Bing Tan; Ziqi Zhong; Guowu Zhan (Chemical Engineering Journal, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Effective use of limestones to reconstruct seawater Li isotope compositions - A community standard proposal - Cheng Cao; Xiao-Ming Liu; Xi-Kai Wang; Jun Chen (Chemical Geology, 2023)

Exploration of the optimal stocking density of red swamp crayfish (Procambarus clarkii) larvae by using the biofloc technology - Jinghao Li; Chen Qian; Chenlu Li; Zhengyou Li; Yewen Xi; Yongxu Cheng; Jiayao Li (Aquaculture International, 2023)

Bisphenol A substitutes and childhood obesity at 7 years: a cross-sectional study in Shandong, China - Minyan Chen; Cheng Lv; Shanyu Zhang; Lap Ah Tse; Xinyu Hong; Xi Liu; Yu Ding; Ping Xiao; Ying Tian; Yu Gao (Environmental Science and Pollution Research, 2023)

Air pollution exposure and heart failure: A systematic review and meta-analysis - Dongdong Zhang; Weiling Chen; Cheng Cheng; Hao Huang; Xi Li; Pei Qin; Chuanqi Chen; Xinping Luo; Ming Zhang; Jing Li; Xizhuo Sun; Yu Liu; et al. (Science of The Total Environment, 2023)

Short-chain fatty acid production and phosphorous recovery from waste activated sludge via anaerobic fermentation: A comparison of in-situ and ex-situ thiosulfate-assisted Fe2+/persulfate pretreatment - Boyi Cheng; Da Zhang; Qingshan Lin; Shihao Xi; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Zongping Wang; Gang Guo (Science of The Total Environment, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

High oil content inhibits humification in food waste composting by affecting microbial community succession and organic matter degradation - Juan Liu; Yujun Shen; Jingtao Ding; Wenhai Luo; Haibin Zhou; Hongsheng Cheng; Huihui Wang; Xi Zhang; Jian Wang; Pengxiang Xu; Qiongyi Cheng; Shuangshuang Ma; et al. (Bioresource Technology, 2023)

Levels, source apportionment, and risk assessment of polycyclic aromatic hydrocarbons in vegetable bases of northwest China - Nuerla Ailijiang; Xi Cui; Anwar Mamat; Yusuyunjiang Mamitimin; Naifu Zhong; Wenhu Cheng; Nanxin Li; Qiongfang Zhang; Miao Pu (Environmental Geochemistry and Health, 2023)

Metabonomic Analysis of Macrobrachium rosenbergii with Iron Prawn Syndrome (IPS) - Xi-Lian Li; Pei-Jing Shen; Wen-Ping Jiang; Ji-Lun Meng; Hai-Hua Cheng; Qiang Gao (Fishes, 2023)
We previously reported on the comparison of proteomic data between seven tissue types of a novel “iron prawn” species. However, no transcripts or metabolic information are available for this species. We therefore performed shotgun LC–MS/MS metabonomic and RNA-seq analyses of the total protein from “iron prawns”. KEGG analysis revealed that the largest group consisted of a total of 114 KEGG pathway proteins, comparing the “iron prawns” with the normal prawns. A total of 423 peptides, corresponding to metabolic pathways, ABC transporters, starch and sucrose metabolism, insulin resistance/secretion, fatty digestion and absorption, and lipid metabolism, were identified. The pathways of carbohydrate and amino acid metabolism decreased in female iron prawns, while organic acid and its derivatives increased. However, the pathway of organic acid and its derivatives decreased and lipid metabolism increased in the male iron prawns. The pathways of choline metabolism in cancer and glycerophospholipid/histidine/propanoate metabolism have been significantly affected in iron prawns. Our work provides insight into the understanding of the formation mechanism of the “iron prawn”.

Mitoquinone protects against acetaminophen-induced liver injury in an FSP1-dependent and GPX4-independent manner - Xue He; Shi-Min Liang; Hong-Qian Wang; Li Tao; Fei-Fei Sun; Yan Wang; Cheng Zhang; Yi-Chao Huang; De-Xiang Xu; Xi Chen (Toxicology and Applied Pharmacology, 2023)

Optimizing waste activated sludge disintegration by investigating multiple electrochemical pretreatment conditions: Performance, mechanism and modeling - Qingshan Lin; Xinlei Dong; Shihao Xi; Boyi Cheng; Feixiang Zan; Jie Ma; Xiaoming Liu; Tianwei Hao; Gang Guo (Science of The Total Environment, 2023)

Luminescent CS-SiO2@TEuTTA membrane for simultaneous detection and adsorption of copper(II) ions - Le Li; Peng Xi; Xiaoqing Wang; Bowen Cheng (Journal of Environmental Chemical Engineering, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Enhancing selective adsorption of CO2 through encapsulating FeTPPs into Cu-BTC - Guangping Lei; Guojun Xi; Zihan Liu; Qibin Li; Huiyuan Cheng; Hantao Liu (Chemical Engineering Journal, 2023)

Enhancing reverse intersystem crossing rate of red thermally activated delayed fluorescence emitters by simultaneously involving locally excited triplet states from donor and acceptor segments - Hui Wang; Xi Zhang; Lu Zhou; Xiao-Chun Fan; Ying-Chun Cheng; Jia Yu; Jia-Xiong Chen; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Chronic oral exposure to short chain chlorinated paraffins induced testicular toxicity by promoting NRF2-mediated oxidative stress - Zhang Qian; Chuwei Li; Wei Zhao; Zhaowanyue He; Mengqi Xue; Shuxian Wang; Xi Cheng; Rujun Ma; Xie Ge (Toxicology Letters, 2023)

Electrophilic components from Xiaoheiyao (rhizomes of Inula nervosa Wall.) alleviate the production of heterocyclic aromatic amines via creatinine inhibition - Xiang-Rong Cheng; Jia-Hui Ma; Issoufou Amadou; Wei Zhao; Yu-Yao Chen; Chen-Xi Zhang; Bin Guan (Food Chemistry, 2023)

Autochthonous Bacillus subtilis and Enterococcus faecalis improved liver health, immune response, mucosal microbiota and red-head disease resistance of yellow drum (Nibea albiflora) - Xi-Yue Ding; Cheng-Ye Wei; Zi-Yan Liu; Hong-Ling Yang; Fang Han; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Investigation of CuCoFe-LDH as an efficient and stable catalyst for the degradation of acetaminophen in heterogeneous electro-Fenton system: Key operating parameters, mechanisms and pathways - Cheng Xue; Zhenhua Cao; Xiaoqin Tong; Peizhen Yang; Songrong Li; Xi Chen; Dongfang Liu; Wenli Huang (Journal of Environmental Management, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Recent advances in lithium extraction from salt lake brine using coupled and tandem technologies - Junxiang Zhang; Zeyu Cheng; Xinbo Qin; Xi Gao; Min Wang; Xu Xiang (Desalination, 2023)

Formation processes of nitrogen-containing organic compounds from heterogeneous reactions of C3H6/NO2/O3 with α-Fe2O3 particles - Xi Xi; Xiang He; Zhi-Cheng Ma; Hui-Qing Ma; Peng-Cheng Liao (Atmospheric Environment, 2023)

Study on the modification effect and mechanism of tailings powder on coal gangue-based mining cementitious filling material - Jisheng Qiu; Xi Luan; Kun Cheng; Xiao Guan; Minmin Yang; Zhijie Xiao (Environmental Science and Pollution Research, 2023)

When Does a Light Sphere Break Ice Plate Most by Using Its Net Buoyance? - Bao-Yu Ni; Hao Tan; Shao-Cheng Di; Chen-Xi Zhang; Zhiyuan Li; Luofeng Huang; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2023)
A free-rising buoyant sphere can break an ice plate floating above it. The problem is when the light sphere breaks the ice plate most, or the optimal relative density of the sphere which can break the ice plate the most severely. This experimental study was done to answer this problem. A set of experimental devices were designed, and a high-speed camera system was adopted to record the whole dynamic process, including the free-rising of the sphere, the collision between the sphere and the ice plate, the crack initiation and propagation, as well as the breakup of the ice plate. The failure mode of the ice plate under impact load was analyzed. It was found that conical cracks were formed under the reflected tensile wave at the top surface of the ice plate. On this basis, the influences of ice thickness, the initial submergence depth, and the relative density of the sphere on icebreaking were further investigated. An optimal relative density of the sphere was found when the sphere was released at a certain initial submergence depth, at which point the ice was damaged the most severely. For example, when the dimensionless initial submergence depth of the sphere was 2.31, the optimal relative density of the sphere was close to 0.4, with the probability of the ice plate breakup as high as 91.7%. It was also found from the experiments that the degree of damage to the ice plate correlated well with the kinetic energy of the sphere just before collision. Results showed that the optimal relative density can be estimated by theoretical analysis of the kinetic energy of the sphere, which will provide a reference for potential icebreaking applications in the future.

Generalized Behavior Decision-Making Model for Ship Collision Avoidance via Reinforcement Learning Method - Wei Guan; Ming-yang Zhao; Cheng-bao Zhang; Zhao-yong Xi (Journal of Marine Science and Engineering, 2023)
Due to the increasing number of transportation vessels, marine traffic has become more congested. According to the statistics, 89% to 95% of maritime accidents are related to human factors. In order to reduce marine incidents, ship automatic collision avoidance has become one of the most important research issues in the field of ocean engineering. A generalized behavior decision-making (GBDM) model, trained via a reinforcement learning (RL) algorithm, is proposed in this paper, and it can be used for ship autonomous driving in multi-ship encounter situations. Firstly, the obstacle zone by target (OZT) is used to calculate the area of future collisions based on the dynamic information of ships. Meanwhile, a virtual sensor called a grid sensor is taken as the input of the observation state. Then, International Regulations for Preventing Collision at Sea (COLREGs) is introduced into the reward function to make the decision-making fully comply with COLREGs. Different from the previous RL-based collision avoidance model, the interaction between the ship and the environment only works in the collision avoidance decision-making stage. Finally, 60 complex multi-ship encounter scenarios clustered by the COLREGs are taken as the ship’s GBDM model training environments. The simulation results show that the proposed GBDM model and training method has flexible scalability in solving the multi-ship collision avoidance problem complying with COLREGs in different scenarios.

Evaluating the significance of amino acids (AAs) in cyanide-treated rice plants under different nitrogen fertilization using the relative importance index of AA - Cheng-Zhi Li; Yu-Xi Feng; Xiao-Zhang Yu (Chemosphere, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Effects of β-amylase hydrolysis on the structural, physicochemical and storage properties of wheat starch - Yan Li; Wen Cheng; Xi Qiu; Yujie Sun; Xuanze Xia; Lianzhan Yang; Mingcong Fan; Li Wang; Haifeng Qian (Journal of Cereal Science, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

Marked shifts of harmful algal blooms in the Bohai Sea linked with combined impacts of environmental changes - Xiao-Yu Li; Ren-Cheng Yu; Anthony J. Richardson; Chaojiao Sun; Ruth Eriksen; Fan-Zhou Kong; Zheng-Xi Zhou; Hui-Xia Geng; Qing-Chun Zhang; Ming-Jiang Zhou (Harmful Algae, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

Structural and antimicrobial property changes of veterinary antibiotics in thermal treatment - Xi Chen; Zhanjun Cheng; Guanyi Chen; Yongkui Yang; Peizhe Sun (Environmental Pollution, 2023)

A mixed selective edge-based smoothed PFEM with second-order cone programming for geotechnical large deformation analysis - Xi-Wen Zhou; Feng-Tao Liu; Yin-Fu Jin; Zhen-Yu Yin; Cheng-Bo Zhang (Computers and Geotechnics, 2023)

High-efficiency emissive dendritic phosphorescent iridium (III) complex with thermally activated delayed fluorescence molecules as functional light-harvesting moieties - Yuchao Liu; Yanchao Xie; Yannan Cheng; Xi Tian; Lei Hua; Shian Ying; Shouke Yan; Zhongjie Ren (Chemical Engineering Journal, 2023)

Spatial-temporal variations of proline and related amino acids reveal distinct nitrogenous utilization strategies in rice during detoxification of exogenous cyanide - Yu-Xi Feng; Cheng-Zhi Li; Li Yang; Xiao-Zhang Yu (Chemico-Biological Interactions, 2023)

Pollution levels, sources and risk assessment of polycyclic aromatic hydrocarbons in farmland soil and crops near Urumqi Industrial Park, Xinjiang, China - Xi Cui; Nuerla Ailijiang; Yusuyunjiang Mamitimin; Naifu Zhong; Wenhu Cheng; Nanxin Li; Qiongfang Zhang; Miao Pu (Stochastic Environmental Research and Risk Assessment, 2023)

CmHY5 functions in apigenin biosynthesis by regulating flavone synthase II expression in chrysanthemum flowers - Chang Luo; Lei Liu; Jian Zhao; Yanjie Xu; Hua Liu; Dongliang Chen; Xi Cheng; Junping Gao; Bo Hong; Conglin Huang; Chao Ma (Planta, 2023)

Cloning and functional identification of pmKPI cDNA in Poecilobdella manillensis - Gui-Yan Shao; Qing-Qing Tian; Wen-Bo Li; Su-Yan Wang; Yu-Xi Lu; Fei Liu; Bo-Xing Cheng (Molecular Biology Reports, 2023)

Transcriptional analysis of heavy metal P1B-ATPases (HMAs) elucidates competitive interaction in metal transport between cadmium and mineral elements in rice plants - Peng Tian; Yu-Xi Feng; Cheng-Zhi Li; Ping Zhang; Xiao-Zhang Yu (Environmental Science and Pollution Research, 2023)

Sand-fixing effect and compound change of nylon checkerboard sand barrier - Cheng Xi; Hejun Zuo; Xianghong Wei; Min Yan (Environmental Science and Pollution Research, 2022)

Effect of dietary cholesterol on ovarian development of Chinese mitten crabs (Eriocheir sinensis) - Huixing Guo; Mangmang Wang; Xi Wang; Kang Xiao; Yangyang Huang; Haokun Hua; Wei Xiong; Wenbin Liu; Kenneth Prudence Abasubong; Wei Qiang; Cheng Chi; Guangzhen Jiang (Frontiers in Marine Science, 2022)
This study was conducted to evaluate the effect of cholesterol (CHO) on ovarian development of Eriocheir sinensis through a feeding trial. Crabs (average weight 43.35 ± 0.05 g) were randomly fed with one of three diets: 0% CHO, 0.4% CHO and 1.6% CHO for 16 weeks. Results indicated that the hepatosomatic index (HSI) and gonad index (GSI) of crabs fed with 0.4% CHO diet were significantly higher than those in the control group. ( P < 0.05). Meanwhile, 0.4% CHO can significantly increase the gene expression of vtg and vgr in ovary ( P < 0.05), thus promoting the accumulation of Vtg. The protein expression of MEK1/2, ERK, p-ERK1/2, Cyclin B and CDC2 were significantly increased in the 0.4% CHO group, therefore dietary CHO might promote oocyte maturation by activating MAPK signal pathway and cooperating with maturation promoting factor (MPF). Further exploration results showed that 0.4% CHO was able to significantly up-regulate the protein expression of STAR and SR-B1 to promote the transport of CHO to ovary, thereby providing sufficient substrates for estradiol (E 2 ) synthesis. In addition, the results in vivo and in vitro shown that CHO could regulate the activities of enzymes such as CYP11A1 and CYP19A1 through the cAMP-PKA-CREB/SF-1 signal pathway and then affects the level of E 2 in the organism. In summary, supplementing the appropriate amount of CHO in the diet can improve the E 2 level of the organism, thus increasing the accumulation of nutrients in the ovary, promoting the completion of meiosis, and finally achieving the purpose of promoting ovarian maturation.

Impact of repeated intravenous infusions of umbilical cord–derived versus bone marrow–derived mesenchymal stem cells on angiogenesis in a pregnant experimentally induced deep venous thrombosis rat model - Xi Cheng; Weina Wang; Rong Du; Mu Zhang; Yuanyuan Xie; Weiwei Sun; Jingjing Ji; Baolan Sun; Yuquan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

Attenuation-compensated reverse time migration of GPR data constrained by resistivity - Hong-Hua Wang; Yu-He Xi; Yu-Zeng Lv; Yu-Cheng Wang (Applied Geophysics, 2022)

Dynamics of extracellular polymeric substances and soil organic carbon with mangrove zonation along a continuous tidal gradient - Dong-Xi Liu; Zhi-Mao Mai; Cui-Ci Sun; Yan-Wu Zhou; Hui-Huang Liao; You-Shao Wang; Hao Cheng (Frontiers in Marine Science, 2022)
The importance of mangroves in blue carbon storage has been widely reported. However, the potential contribution of microbial extracellular polymeric substances (EPS) to the carbon pool is still poorly understood in mangrove ecosystems. Thus, a natural mangrove reserve located in Gaoqiao was chosen to investigate the linkage between microbial EPS and sediment organic carbon. Sequential resin extraction, Fourier transform infrared spectroscopy (FTIR), and 16S high-throughput sequencing were employed to determine the variations in EPS and bacterial taxa in different mangrove communities. Both EPS and EPS-C increased significantly with mangrove zonation from seaward to landward, irrespective of the EPS subfractions (colloidal and bound EPS) and components (extracellular protein and polysaccharide). Moreover, both EPS and EPS-C were found to be positively correlated with soil organic carbon. The present data further showed that EPS-C accounted for 1.84~10.69% of TOC in surface sediments. Multiple functional groups (e.g., O-H, N-H, and C=O), which may provide ligands for particle adsorption and complexation, were identified by FTIR. Consistent with the ascend of EPS with mangrove zonation from seaward to landward, the highest transmittance intensity for all functional groups was consistently exhibited in EPS isolated from landward Rhizophoraceae forest. In addition, the present data also indicated an interesting positive linkage between EPS and the abundance of some specific bacterial taxa, such as Rhizobiales, Corynebacteriales, and Gaiellales. In summary, this study claims the importance of EPS in the carbon pool in mangrove ecosystems. The present study may provide a better understanding of the functions of mangroves in carbon stocks.

Glucose-6-phosphate dehydrogenase promotes the infection of Chilli veinal mottle virus through affecting ROS signaling in Nicotiana benthamiana - Daoyong Yang; Qiding Peng; Yongchao Cheng; Dehui Xi (Planta, 2022)

Ambient fine particulate pollution hysteresis triggers wake-up stroke and rapidly triggers non-wake-up stroke: a case-crossover study - Yan Wang; Yuan Xin; Xi-Xi Wang; Yu-Lei Zhang; Yue Zhang; Yu Wang; Li Peng; Yun-Cheng Wu (Environmental Science and Pollution Research, 2022)

Degradation of carbamazepine by high-voltage direct current gas–liquid plasma with the addition of H2O2 and Fe2+ - Jinming Yu; Weiwen Yan; Bin Zhu; Zimu Xu; Shuheng Hu; Wenhao Xi; Yan Lan; Wei Han; Cheng Cheng (Environmental Science and Pollution Research, 2022)

Quantitative microbial risk assessment with nasal/oral breathing pattern for S. aureus bioaerosol emission from aeration tanks and residual sludge storage yard in a wastewater treatment plant - Cheng Yan; Xiao-yan Zhao; Xi Luo; Dong-zi An; Hao Zhu; Ming Li; Xiao-jun Ai; Wajid Ali (Environmental Science and Pollution Research, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Effect of formulation on the indoxacarb and lufenuron dissipation in maize and risk assessment - Xi Cheng; Jinjing Xiao; Yuanhui Liu; Qun Gao; Qingkui Fang; Min Liao; Bing Liang; Zhendi Hu; Haiqun Cao (Environmental Science and Pollution Research, 2022)

Molecular functional analyses of larval adhesion in a highly fouling invasive model ascidian - Jiawei Cheng; Shiguo Li; Xi Li; Ruiying Fu; Xuena Huang; Aibin Zhan (Marine Biology, 2022)

Increased Renal Dysfunction, Apoptosis, and Fibrogenesis Through Sympathetic Hyperactivity After Focal Cerebral Infarction - Yingyuan Cai; Xiaowei Lu; Xi Cheng; Qiushi Lv; Gelin Xu; Xinfeng Liu (Translational Stroke Research, 2022)

Armochaetoglasins J and K: new cytochalasans from Chaetomium globosum - Li Cheng; Xi Zheng; Qin Li; Meng-Sha Wei; Chun-Mei Chen; Hu-Cheng Zhu; Chang-Li Zeng; Xin-Cai Hao; Yong-Hui Zhang (Natural Product Research, 2022)

Study on the LAI and FPAR inversion of maize from airborne LiDAR and hyperspectral data - Juncheng Shi; Cheng Wang; Jinliang Wang; Xiaohuan Xi; Xuebo Yang; Xue Ding (International Journal of Remote Sensing, 2022)

Erratum to: Temporal changes in wetland plant communities with decades of cumulative water pollution in two plateau lakes in China’s Yunnan Province - Si-hai Wang; Chao Wu; De-rong Xiao; Juan Wang; Xi-ping Cheng; Fang-bin Guo (Journal of Mountain Science, 2022)

Myd88 knockdown with RNA interference induces in vitro immune hyporesponsiveness in dendritic cells from rhesus monkeys - Qiuhong Wang; Dongyun Cun; Desong Xu; Liang Lin; Jian Jiao; Li Zhang; Cheng Xi; Wei Li; Peng Chen; Mingdao Hu (Immunogenetics, 2022)

Alteromonas oceanisediminis sp. nov., isolated from deep-sea sediment - Xiao-Yu Zhang; Zhen Wang; Jun-Hui Cheng; Hui-Hui Fu; Yu-Zhong Zhang; Xiu-Lan Chen; Xi-Ying Zhang; Xiao-Yan Song; Yu-Qiang Zhang; Fei Xu (Archives of Microbiology, 2022)

D609 inhibition of phosphatidylcholine-specific phospholipase C attenuates prolonged insulin stimulation-mediated GLUT4 downregulation in 3T3-L1 adipocytes - Jinhui Ma; Xu Zhang; Yankun Song; Yan Qin; Yinghui Tan; Lishuang Zheng; Baoqian Cheng; Xin Xi (Journal of Physiology and Biochemistry, 2022)
Glucose uptake is stimulated by insulin via stimulation of glucose transporter 4 (GLUT4) translocation to the plasma membrane from intracellular compartments in adipose tissue and muscles. Insulin stimulation for prolonged periods depletes GLUT4 protein, particularly in highly insulin-responsive GLUT4 storage vesicles. This depletion mainly occurs via H 2 O 2 -mediated retromer inhibition. However, the post-receptor mechanism of insulin activation of oxidative stress remains unknown. Here, we show that phosphatidylcholine-specific phospholipase C (PC-PLC) plays an important role in insulin-mediated downregulation of GLUT4. In the study, 3T3-L1 adipocytes were exposed to a PC-PLC inhibitor, tricyclodecan-9-yl-xanthogenate (D609), for 30 min prior to the stimulation with 500 nM insulin for 4 h, weakening the depletion of GLUT4. D609 also prevents insulin-driven H 2 O 2 generation in 3T3-L1 adipocytes. Exogenous PC-PLC and its product, phosphocholine (PCho), also caused GLUT4 depletion and promoted H 2 O 2 generation in 3T3-L1 adipocytes. Furthermore, insulin-mediated the increase in the cellular membrane PC-PLC activity was observed in Amplex Red assays. These results suggested that PC-PLC plays an important role in insulin-mediated downregulation of GLUT4 and that PCho may serve as a signaling molecule.

Subcellular localization and identification of acyl-CoA: lysophosphatidylethanolamine acyltransferase (LPEAT) in the arachidonic acid-rich green microalga, Myrmecia incisa Reisigl - Yi Liu; Hong Bao; Mei-Li Zhu; Cheng-Xi Hu; Zhi-Gang Zhou (Journal of Applied Phycology, 2022)

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Organic geochemical characteristics and shale oil geological significance of E1f4 in the GY1 well, Guanzhen subsag, Subei basin - Qingsong Cheng; Xi Chen; Jiehui Zhang; Yubing Ji; Dongtao Zhang; Fangyu He; Yangzhi Shi; Chao Zhang (Arabian Journal of Geosciences, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

New monoterpenoids from the stigmas of Crocus sativus - Qing-Wei Fang; Wen-Wei Fu; Jin-Ling Yang; Yue Lu; Jiang-Cheng Chen; Pei-Ying Wu; Xue Zhang; Hong-Xi Xu (Journal of Natural Medicines, 2022)

Applications of CRISPR/Cas gene-editing technology in yeast and fungi - Binyou Liao; Xi Chen; Xuedong Zhou; Yujie Zhou; Yangyang Shi; Xingchen Ye; Min Liao; Ziyi Zhou; Lei Cheng; Biao Ren (Archives of Microbiology, 2022)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Proteomic Response to Environmental Stresses in the Stolon of a Highly Invasive Fouling Ascidian - Xi Li; Shiguo Li; Jiawei Cheng; Ruiying Fu; Aibin Zhan (Frontiers in Marine Science, 2021)
Ascidians, particularly those highly invasive ones, are typical fouling organisms to cause significantly negative ecological and economic influence in coastal ecosystems. Stolon, which is the unique structure of some solitary ascidians to complete the essential process of adhesion, possesses extremely high tolerance to environmental stresses during biofouling and invasions. However, the mechanisms underlying environmental tolerance remain largely unknown. Here, we used the quantitative proteomics technology, isobaric tags for relative and absolute quantitation (iTRAQ), to investigate the molecular response to environmental challenges (temperature and salinity) in the stolon of a highly invasive fouling ascidian, Ciona robusta . When compared with the control, a total of 75, 86, 123, and 83 differential abundance proteins were identified under low salinity, high salinity, low temperature, and high temperature stress, respectively. Bioinformatic analyses uncovered the key pathways under both temperature and salinity stresses, including “cytoskeleton,” “signal transduction,” and “posttranslational modification,” which were involved in stolon structure stability, protein synthesis, and stress response activation. Under the low salinity stress, the “extracellular matrix” pathway was identified to play a crucial role by regulating cell signal transduction and protein synthesis. To deal with the high salinity stress, stolon could store more energy by activating “carbohydrate/lipid transport” and “catabolism” pathways. The energy generated by “lipid metabolism” pathway might be beneficial to resist the low temperature stress. The upregulation of “cell cycle” pathway could inhibit cell growth, thus helping stolon conserve more energy against the high temperature stress. Our results here provide valuable references of candidate pathways and associated genes for studying mechanisms of harsh environmental adaptation and developing antifouling strategies in marine and coastal ecosystems.

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Pesticides Exposure and Dopaminergic Neurodegeneration - Jingsong Xiao; Xunhu Dong; Xi Zhang; Feng Ye; Jin Cheng; Guorong Dan; Yuanpeng Zhao; Zhongmin Zou; Jia Cao; Yan Sai (Exposure and Health, 2021)

Novel Dicistroviruses in an Unexpected Wide Range of Invertebrates - Ruo-Lin Cheng; Xiao-Feng Li; Chuan-Xi Zhang (Food and Environmental Virology, 2021)

A Comprehensive Risk Assessment Framework for Inland Waterway Transportation of Dangerous Goods - Xi Huang; Yuanqiao Wen; Fan Zhang; Zhongyi Sui; Xiaodong Cheng (Journal of Marine Science and Engineering, 2021)
A framework for risk assessment due to inland waterway transportation of dangerous goods is designed based on all possible event types that may be caused by the inland transportation of dangerous goods. The objective of this study is to design a framework for calculating the risks associated with changes in the transportation of dangerous goods along inland waterways. The framework is based on the traditional definition of risk and is designed for sensitive riverside environmental conditions in inland waterways. From the perspective of transportation management, this paper introduced the concept of transportability of dangerous goods and constructed a transportability assessment framework, which consists of a multi-index evaluation system and a single metric model. The result of the assessment is as an auxiliary basis to determine the transportation permit and control intensity of dangerous goods in an inland waterway specific voyage. The methodology is illustrated using a case study of transporting fireworks in the Yangtze River.

Removal of N,N-dimethylformamide by dielectric barrier discharge plasma combine with manganese activated carbon - Wenjiao Sang; Longjie Mei; Cheng Zhan; Qian Zhang; Xi Jin; Shaohui Zhang; Shiyang Zhang; Cuihua Li; Min Li (Environmental Science and Pollution Research, 2021)

A comparison of hepatotoxicity induced by different lengths of tungsten trioxide nanorods and the protective effects of melatonin in BALB/c mice - Lin Mao; Lifang Zheng; Huihui You; Muhammad Wajid Ullah; Haoyan Cheng; Qing Guo; Zhihong Zhu; Zhuge Xi; Rui Li (Environmental Science and Pollution Research, 2021)

Nitrogen removal from domestic wastewater using core-shell anthracite/Mg-layered double hydroxides (LDHs) in constructed wetlands - Jing Cheng; Xiangling Zhang; Yuqi Tang; Zan Song; Yinghe Jiang; Zhouying Xu; Xi Jin (Environmental Science and Pollution Research, 2021)

Serum Progesterone and Testosterone Levels in Schizophrenia Patients at Different Stages of Treatment - Wei Huang; Yong-Hang Li; Shi-Qing Huang; Hui Chen; Zai-Fang Li; Xi-Xi Li; Xue-Song Li; Yong Cheng (Journal of Molecular Neuroscience, 2021)

Near-Surface Geothermal Reservoir Imaging based on the Customized Dense Seismic Network - Changjiang Zhou; Jianghai Xia; Jingyin Pang; Feng Cheng; Xinhua Chen; Chaoqiang Xi; Hongyu Zhang; Ya Liu; Ling Ning; Tianyu Dai; Binbin Mi; Changwei Zhou (Surveys in Geophysics, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

The Alleviative Effects of Quercetin on Cadmium-Induced Necroptosis via Inhibition ROS/iNOS/NF-κB Pathway in the Chicken Brain - Lili Liu; Yuan Liu; Xi Cheng; Xinyuan Qiao (Biological Trace Element Research, 2021)

Prediction of sound pressure fluctuations in the start-up phase of thermoacoustic oscillations under external perturbation - Zi-Hua Liu; Hao Zhou; Cheng-Fei Tao; Muhammad Waryal Dahri; Ming-Xi Zhou (Waste Disposal & Sustainable Energy, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Estimation of rice plant potassium accumulation based on non-negative matrix factorization using hyperspectral reflectance - Jingshan Lu; Wanyu Li; Minglei Yu; Xiangbin Zhang; Yong Ma; Xi Su; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Precision Agriculture, 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

Interdecadal variability in ecosystem health of Changjiang (Yangtze) River estuary using estuarine biotic integrity index - Shouhai Liu; Haijing Zhang; Yanlong He; Xiangsheng Cheng; Haofei Zhang; Yutao Qin; Xi Ji; Riguang He; Yaohui Chen (Journal of Oceanology and Limnology, 2021)

Comparative genomic analysis of superoxide dismutase (SOD) genes in three Rosaceae species and expression analysis in Pyrus bretschneideri - Guohui Li; Fei Hu; Yang Zhang; Yu Zhao; Han Wang; Tianzhe Chen; Xi Cheng; Yongping Cai (Physiology and Molecular Biology of Plants, 2021)

Metagenomics analysis of the gut microbiome in healthy and bacterial pneumonia forest musk deer - Wei Zhao; Ziwei Ren; Yan Luo; Jianguo Cheng; Jie Wang; Yin Wang; Zexiao Yang; Xueping Yao; Zhijun Zhong; Wei Yang; Xi Wu (Genes & Genomics, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

A New Endoplasmic Reticulum (ER)-Targeting Fluorescent Probe for the Imaging of Cysteine in Living Cells - Lei Zhou; Yunxia Li; Aiqin Zhou; Guanghui Zhang; Zhi-Qiang Cheng; Yong-Xi Ge; Shan-Kui Liu; Ricardo Bentes Azevedo; Juan Zhang; Shenglin Jiang; Cheng-Shi Jiang (Journal of Fluorescence, 2020)

Anxiety is associated with increased risk for atrial cardiopathy - Zhaolu Wang; Huiyuan Qin; Guilin Chen; Yan Dai; Yingyuan Cai; Xi Cheng; Yun Qian; Ming Chu; Xiaowei Lu (Acta Neurologica Belgica, 2020)

Correction to: Genome-wide characterization of the cellulose synthase gene superfamily in Pyrus bretschneideri and reveal its potential role in stone cell formation - Guohui Li; Xin Liu; Yuxuan Liang; Yang Zhang; Xi Cheng; Yongping Cai (Functional & Integrative Genomics, 2020)

A calculation model to assess the crack propagation length of rock block in clastic flow - Yang Liu; Yong You; Jin-feng Liu; Shu-xi Zhao; Dong-xu Yang; Dao-chuan Liu; Lin Liu; Yan-fang Xie; Kai-cheng Yang (Journal of Mountain Science, 2020)

Distinct lung microbial community states in patients with pulmonary tuberculosis - Yongfeng Hu; Ying Kang; Xi Liu; Min Cheng; Jie Dong; Lilian Sun; Yafang Zhu; Xianwen Ren; Qianting Yang; Xinchun Chen; Qi Jin; Fan Yang (Science China Life Sciences, 2020)

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Genome-wide characterization of the cellulose synthase gene superfamily in Pyrus bretschneideri and reveal its potential role in stone cell formation - Guohui Li; Xin Liu; Yuxuan Liang; Yang Zhang; Xi Cheng; Yongping Cai (Functional & Integrative Genomics, 2020)

Chiral resolution and bioactivity of enantiomeric furofuran lignans from Juglans mandshurica Maxim - Jie Wang; Le Zhou; Zhuo-Yang Cheng; Yu-Xi Wang; Zhi-Yang Yan; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Ochratoxin A in human blood plasma samples from apparently healthy volunteers in Nanjing, China - Kai Fan; Xi Cheng; Wenbo Guo; Xing Liu; Zhiqi Zhang; Qi Yao; Dongxie Nie; Bing Yao; Zheng Han (Mycotoxin Research, 2020)

The effect of follower load on the range of motion, facet joint force, and intradiscal pressure of the cervical spine: a finite element study - Xin-Yi Cai; Chen-Xi YuChi; Cheng-Fei Du; Zhong-Jun Mo (Medical & Biological Engineering & Computing, 2020)

Blood and Cerebrospinal Fluid Autoantibody to Aβ Levels in Patients with Alzheimer’s Disease: a Meta-Analysis Study - Xiao-Wan Li; Xi-Xi Li; Qing-Shan Liu; Yong Cheng (Journal of Molecular Neuroscience, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Neuroprotective effects of miR-532-5p against ischemic stroke - Jingwei Mu; Xi Cheng; Shanshan Zhong; Xiaohong Chen; Chuansheng Zhao (Metabolic Brain Disease, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Monitoring leaf potassium content using hyperspectral vegetation indices in rice leaves - Jingshan Lu; Tiancheng Yang; Xi Su; Hao Qi; Xia Yao; Tao Cheng; Yan Zhu; Weixing Cao; Yongchao Tian (Precision Agriculture, 2020)

Metabolomic abnormalities of purine and lipids implicated olfactory bulb dysfunction of CUMS depressive rats - Yong He; Yue Wang; Zhonghao Wu; Tianlan Lan; Yu Tian; Xi Chen; Yan Li; Ruozhi Dang; Mengge Bai; Ke Cheng; Peng Xie (Metabolic Brain Disease, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Separation and preparation of N-glycans based on ammonia-catalyzed release method - Meifang Yang; Ming Wei; Chengjian Wang; Yu Lu; Wanjun Jin; Xi Gao; Cheng Li; Langhong Wang; Linjuan Huang; Zhongfu Wang (Glycoconjugate Journal, 2020)

Exploration of targets regulated by miR-125b in porcine adipocytes - Xiao Cheng; Xingping Chen; Peng Wang; Ting Chen; Jiajie Sun; Qianyun Xi; Yongliang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Effect of miR-27b-5p on apoptosis of human vascular endothelial cells induced by simulated microgravity - Yi-Kai Pan; Cheng-Fei Li; Yuan Gao; Yong-Chun Wang; Xi-Qing Sun (Apoptosis, 2020)
Weightlessness-induced cardiovascular dysfunction can lead to physiological and pathological consequences. It has been shown that spaceflight or simulated microgravity can alter expression profiles of some microRNAs (miRNAs). Here, we attempt to identify the role of miRNAs in human umbilical vein endothelial cells (HUVECs) apoptosis under simulated microgravity. RNA-sequencing and quantitative real-time PCR (qRT-PCR) assays were used to identify differentially expressed miRNAs in HUVECs under simulated microgravity. Then we obtained the target genes of these miRNAs through target analysis software. Moreover, GO and KEGG enrichment analysis were performed. The effects of these miRNAs on HUVECs apoptosis were evaluated by flow cytometry, Western blot and Hoechst staining. Furthermore, we obtained the target gene of miR-27b-5p by luciferase assay, qRT-PCR and Western blot. Finally, we investigated the relationship between this target gene and miR-27b-5p in HUVECs apoptosis under normal gravity or simulated microgravity. We found 29 differentially expressed miRNAs in HUVECs under simulated microgravity. Of them, the expressions of 3 miRNAs were validated by qRT-PCR. We demonstrated that miR-27b-5p affected HUVECs apoptosis by inhibiting zinc fingers and homeoboxes 1 (ZHX1). Our results reported here demonstrate for the first time that simulated microgravity can alter the expression of some miRNAs in HUVECs and miR-27b-5p may protect HUVECs from apoptosis under simulated microgravity by targeting ZHX1.

Baeckeins L and M, two novel C -methylated triflavonoids from the roots of Baeckea frutescens L. - Cheng-Jun Jia; Xiao-Min Sun; Xiang-Yun Zhang; Zi-Jiao Wei; Bei-Xi Jia (Natural Product Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Crocin attenuates isoprenaline-induced myocardial fibrosis by targeting TLR4/NF-κB signaling: connecting oxidative stress, inflammation, and apoptosis - Weiyue Jin; Yuanyuan Zhang; Yurun Xue; Xue Han; Xuan Zhang; Zhihong Ma; Shijiang Sun; Xi Chu; Jie Cheng; Shengjiang Guan; Ziliang Li; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Classification of tight sandstone reservoirs based on NMR logging - Chang-Xi Li; Mi Liu; Bin-Cheng Guo (Applied Geophysics, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Purification and characterization of an endo-xylanase from Trichoderma sp., with xylobiose as the main product from xylan hydrolysis - Li-Hao Fu; Nan Jiang; Cheng-Xi Li; Xue-Mei Luo; Shuai Zhao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2019)

A new flavanone glycoside isolated from Tournefortia sibirica - Shengbao Diao; Mei Jin; Chun Shi Jin; Cheng-Xi Wei; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2019)

Application of Biodegradable Materials in Orthopedics - Jun-Wei Li; Cheng-Fei Du; Chen-Xi Yuchi; Chun-Qiu Zhang (Journal of Medical and Biological Engineering, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Autophagy protects HUVECs against ER stress-mediated apoptosis under simulated microgravity - Cheng-Fei Li; Yi-Kai Pan; Yuan Gao; Fei Shi; Yong-Chun Wang; Xi-Qing Sun (Apoptosis, 2019)

Adventitious root cultures from leaf explants of Helicteres angustifolia L. as a novel source for production of natural bioactive compounds - Xi Yang; Jingtong Zhang; Zhongfang Lei; Xuefei Yan; Xuansheng Hu; Delin Cheng; Zhenya Zhang (Acta Physiologiae Plantarum, 2019)

Fine mapping and candidate gene analysis of qhkw5-3, a major QTL for kernel weight in maize - Wenliang Li; Qinghe Bai; Weimin Zhan; Chenyu Ma; Shunyou Wang; Yuanyuan Feng; Mengdi Zhang; Ying Zhu; Ming Cheng; Zhangying Xi (Theoretical and Applied Genetics, 2019)

Dysregulation of Fibroblast Growth Factor 10 in the Peripheral Blood of Patients with Schizophrenia - Yun Yu; Guo-Jun Xie; Yang Hu; Xue-Song Li; Guang-Yang Chen; Guang-En Zheng; Xi Chen; Yong Cheng (Journal of Molecular Neuroscience, 2019)

Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Yang-Shuo Tang; Yan-Hua Zhao; Yong Zhong; Xiao-Zhao Li; Jia-Xi Pu; Yan-Cheng Luo; Qiao-Ling Zhou (Inflammation Research, 2019)

Assessing effects of “source-sink” landscape on non-point source pollution based on cell units of a small agricultural catchment - Jin-liang Wang; Cheng-long Chen; Jiu-pai Ni; De-ti Xie; Xi Guo; Zhi-jun Luo; Yue Zhao (Journal of Mountain Science, 2019)

Quaternary ammonium-functionalized rice straw hydrochar as efficient adsorbents for methyl orange removal from aqueous solution - Xiong Peng; Zongcheng Yan; Xi Cheng; Yu Li; Aili Wang; Li Chen (Clean Technologies and Environmental Policy, 2019)

Establishment of transgenic marigold using the floral dip method - Xi Cheng; Conglin Huang; Xiuhai Zhang; Yingmin Lyu (Acta Physiologiae Plantarum, 2019)

Human genome-derived TOP1 matrix attachment region enhances transgene expression in the transfected CHO cells - Yan-Long Jia; Xiao Guo; Xi-Cheng Wang; Tian-Yun Wang (Biotechnology Letters, 2019)

Lutein content in petals and leaves of marigold and analysis of lutein synthesis gene expression - Xi Cheng; Xuezhi Zhao; Conglin Huang; Xiuhai Zhang; Yingmin Lyu (Acta Physiologiae Plantarum, 2019)

Identification of sedimentary-diagenetic facies and implications for reservoir quality: evidence from the Eocene coarse-grained deposits in the Dongying Depression, Bohai Bay Basin, China - Yanzhong Wang; Yingchang Cao; Benben Ma; Kelai Xi; Xin Cheng; Mingshui Song (Geosciences Journal, 2019)

Disruption of a Upf1-like helicase-encoding gene OsPLS2 triggers light-dependent premature leaf senescence in rice - Pan Gong; Yanmin Luo; Fudeng Huang; Yaodong Chen; Chaoyue Zhao; Xin Wu; Kunyu Li; Xi Yang; Fangmin Cheng; Xun Xiang; Chunyan Wu; Gang Pan (Plant Molecular Biology, 2019)

Carbon concentrations and their stable isotopic signatures in the upper Han River, China - Xi Han; Xiaoli Cheng; Siyue Li; Jie Yuan; Quanfa Zhang (Environmental Science and Pollution Research, 2019)

Diffuse Intrinsic Pontine Gliomas Exhibit Cell Biological and Molecular Signatures of Fetal Hindbrain-Derived Neural Progenitor Cells - Yu Sun; Cheng Xu; Changcun Pan; Xin Chen; Yibo Geng; Yuliang Wu; Peng Zhang; Wenhao Wu; Yu Wang; Deling Li; Zhen Wu; Junting Zhang; et al. (Neuroscience Bulletin, 2019)

Family-1 UDP glycosyltransferases in pear (Pyrus bretschneideri): Molecular identification, phylogenomic characterization and expression profiling during stone cell formation - Xi Cheng; Abdullah Muhammad; Guohui Li; Jingyun Zhang; Jun Cheng; Jingxiang Qiu; Taoshan Jiang; Qing Jin; Yongping Cai; Yi Lin (Molecular Biology Reports, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Development of a reverse genetics system for a feline panleukopenia virus - Nan Cheng; Yongkun Zhao; Qiuxue Han; Weijiao Zhang; Ji Xi; Yongle Yu; Hualei Wang; Guohua Li; Yuwei Gao; Songtao Yang; Weiquan Liu; Xianzhu Xia (Virus Genes, 2019)

A new benzofuran from Artemisia halodendron Turcz. ex Bess. - Jinfeng Sun; Wei Zhou; Cheng-Xi Wei; Zhihong Zhang; Xuejun Jin; Gao Li (Natural Product Research, 2019)

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Degradation of Phenol in Water Using a Novel Gas-Liquid Two-Phase Dielectric Barrier Discharge Plasma Reactor - Han Zhang; Yanan Liu; Xi Cheng; Ai Zhang; Xiang Li; Jinxia Liu; Shijie Cai; Cheng Yang; Stéphanid Ognier; Pan Li (Water, Air, & Soil Pollution, 2018)

BrFLC5: a weak regulator of flowering time in Brassica rapa - Xi Xi; Keyun Wei; Baozhen Gao; Jiahe Liu; Jianli Liang; Feng Cheng; Xiaowu Wang; Jian Wu (Theoretical and Applied Genetics, 2018)

Performance and biofilm characteristics of biotrickling filters for ethylbenzene removal in the presence of saponins - Hui Qian; Yan Cheng; Chunping Yang; Shaohua Wu; Guangming Zeng; Jinying Xi (Environmental Science and Pollution Research, 2018)

Effects of Warming and Nitrogen Addition on Plant Photosynthate Partitioning in an Alpine Meadow on the Tibetan Plateau - Ning Zong; Xi Chai; Pei-Li Shi; Xiao-Cheng Yang (Journal of Plant Growth Regulation, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

The ammonia-catalyzed release of glycoprotein N-glycans - Chengjian Wang; Meifang Yang; Xi Gao; Cheng Li; Zihua Zou; Jianli Han; Linjuan Huang; Zhongfu Wang (Glycoconjugate Journal, 2018)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Iodine-Rich Herbs and Potassium Iodate Have Different Effects on the Oxidative Stress and Differentiation of TH17 Cells in Iodine-Deficient NOD.H-2h4 Mice - Cheng-han Gao; Jin-qiao Qu; Xi-yu Zhou; Tian-shu Gao (Biological Trace Element Research, 2018)

Using maximum likelihood to derive various distance-based goodness-of-fit indicators for hydrologic modeling assessment - Qin-Bo Cheng; Xi Chen; Chong-Yu Xu; Zhi-Cai Zhang; Christian Reinhardt-Imjela; Achim Schulte (Stochastic Environmental Research and Risk Assessment, 2018)

Low-dose diethylhexyl phthalate exposure does not impair the expressive patterns of epigenetics-related genes and DNA methylation of breast cancer-related genes in mouse mammary glands - Shun-Feng Cheng; Ling Li; Bo Li; Jing-Cai Liu; Fang-Nong Lai; Yong Zhao; Xi-Feng Zhang; Wei Shen; Lan Li (Molecular & Cellular Toxicology, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Anti-proliferative and pro-apoptotic effects of cinobufagin on human breast cancer MCF-7 cells and its molecular mechanism - Ling Zhu; Yuxin Chen; Cheng Wei; Xi Yang; Jing Cheng; Zhimin Yang; Chuanrong Chen; Zhaoning Ji (Natural Product Research, 2018)

Comparative Transcriptome Analysis Provides Insights into Differentially Expressed Genes and Long Non-Coding RNAs between Ovary and Testis of the Mud Crab (Scylla paramamosain) - Xiaolong Yang; Mhd Ikhwanuddin; Xincang Li; Fan Lin; Qingyang Wu; Yueling Zhang; Cuihong You; Wenhua Liu; Yinwei Cheng; Xi Shi; Shuqi Wang; Hongyu Ma (Marine Biotechnology, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Transgenic cotton co-expressing chimeric Vip3AcAa and Cry1Ac confers effective protection against Cry1Ac-resistant cotton bollworm - Wen-bo Chen; Guo-qing Lu; Hong-mei Cheng; Chen-xi Liu; Yu-tao Xiao; Chao Xu; Zhi-cheng Shen; Mario Soberón; Alejandra Bravo; Kong-ming Wu (Transgenic Research, 2017)

Overexpression of a maize MYB48 gene confers drought tolerance in transgenic arabidopsis plants - Yan Wang; Qianqian Wang; MingLi Liu; Chen Bo; Xi Wang; Qing Ma; Beijiu Cheng; Ronghao Cai (Journal of Plant Biology, 2017)

Secretion of Down Syndrome Critical Region 1 Isoform 4 in Ischemic Retinal Ganglion Cells Displays Anti-Angiogenic Properties Via NFATc1-Dependent Pathway - Yue Xu; Boyu Yang; Yaguang Hu; Lin Lu; Xi Lu; Jiawei Wang; Qinmeng Shu; Qiaochu Cheng; Shanshan Yu; Fan Xu; Jingjing Huang; Xiaoling Liang (Molecular Neurobiology, 2017)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

Deletion of TpKu70 facilitates gene targeting in Talaromyces pinophilus and identification of TpAmyR involvement in amylase production - Ting Zhang; Shuai Zhao; Lu-Sheng Liao; Cheng-Xi Li; Gui-Yan Liao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Abscisic acid negatively regulates post-penetration resistance of Arabidopsis to the biotrophic powdery mildew fungus - Xiang Xiao; Xi Cheng; Kangquan Yin; Huali Li; Jin-Long Qiu (Science China Life Sciences, 2017)

Genome size estimations in Chrysanthemum and correlations with molecular phylogenies - Chang Luo; Dongliang Chen; Xi Cheng; Huien Zhao; Conglin Huang (Genetic Resources and Crop Evolution, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

Variations and changes of annual precipitation in Central Asia over the last century - Zengyun Hu; Qiming Zhou; Xi Chen; Cheng Qian; Shanshan Wang; Jianfeng Li (International Journal of Climatology, 2017)
This study examines the temporal variations and spatial distributions of annual precipitation over Central Asia during the periods of 1901–2013, 1951–2013, and 1979–2013 using the latest version of Global Precipitation Climatology Centre (GPCC) full data reanalysis version 7 ( GPCC V7 ) data set. The linear trend and multiperiods of the precipitation over the entire region and plain and mountainous area separately are analysed by linear least square method and ensemble empirical mode decomposition method. An overall increasing trend [0.66 mm (10 years) −1 ] is found for the entire region during 1901–2013, which is smaller than that of 1951–2013. The regional annual precipitation exhibits multi‐decadal variations, with a sharp decline during 1901–1944, followed by an increase until 1980s, and a fluctuation thereafter. During 1979–2013, the mountainous area shows a greater increasing trend than the entire region. Furthermore, the regional annual precipitation has exhibited high‐frequency variations with 3‐year and 6‐year quasiperiods and a low‐frequency variation with 28‐year quasiperiods. In terms of the spatial distribution, increasing trend in the annual precipitation is found in Xinjiang and decreasing trends appear over the five countries of Central Asia during 1951–2013. Empirical orthogonal function results show that the mountainous area is the large variability centre of the annual precipitation. The dominant mode of interannual variability in Central Asia annual precipitation is related to El Niño‐Southern Oscillation, which explains about 17% of the interannual variance during 1951–2013. The results of this study describe the long‐term variation in the annual precipitation over Central Asia as well as its relationship with some key climate indices in great detail, which will benefit the understanding and the prediction of the climate variations in this region.

Long-Term Generation Scheduling of Hydropower System Using Multi-Core Parallelization of Particle Swarm Optimization - Sheng-li Liao; Ben-xi Liu; Chun-tian Cheng; Zhi-fu Li; Xin-yu Wu (Water Resources Management, 2017)

IL-33 Exerts Neuroprotective Effect in Mice Intracerebral Hemorrhage Model Through Suppressing Inflammation/Apoptotic/Autophagic Pathway - Yuan Gao; Lu Ma; Cheng-liang Luo; Tao Wang; Ming-yang Zhang; Xi Shen; Huan-huan Meng; Meng-meng Ji; Zu-feng Wang; Xi-ping Chen; Lu-yang Tao (Molecular Neurobiology, 2017)

MiR-9 enhances the sensitivity of A549 cells to cisplatin by inhibiting autophagy - Yan Zhang; Xia Meng; Cheng Li; Zhoulin Tan; Xinwei Guo; Zhiting Zhang; Tao Xi (Biotechnology Letters, 2017)

Temporal changes in wetland plant communities with decades of cumulative water pollution in two plateau lakes in China’s Yunnan Province - Si-hai Wang; Chao Wu; De-rong Xiao; Juan Wang; Xi-ping Cheng; Fang-bin Guo (Journal of Mountain Science, 2017)

The complete mitochondrial genome of the monophagous moth Protegira songi (Lepidoptera: Noctuidae) - Guo Xiao-Hui; Cheng Ming-Yang; Hou Ya-Feng; Deng Tuan-Tuan; Zhao Sha; Yu Hai-Li; Xing Lian-Xi (Conservation Genetics Resources, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Comparative analysis of the transcriptional responses to low and high temperatures in three rice planthopper species - Hai‐Jian Huang; Jian Xue; Ji‐Chong Zhuo; Ruo‐Lin Cheng; Hai‐Jun Xu; Chuan‐Xi Zhang (Molecular Ecology, 2017)
The brown planthopper ( Nilaparvata lugens , BPH ), white‐backed planthopper ( Sogatella furcifera , WBPH ) and small brown planthopper ( Laodelphax striatellus , SBPH ) are important rice pests in Asia. These three species differ in thermal tolerance and exhibit quite different migration and overwintering strategies. To understand the underlying mechanisms, we sequenced and compared the transcriptome of the three species under different temperature treatments. We found that metabolism‐, exoskeleton‐ and chemosensory‐related genes were modulated. In high temperature (37 °C), heat shock protein ( HSP ) genes were the most co‐regulated; other genes related with fatty acid metabolism, amino acid metabolism and transportation were also differentially expressed. In low temperature (5 °C), the differences in gene expression of the genes for fatty acid synthesis, transport proteins and cytochrome P450 might explain why SBPH can overwinter in high latitudes, while BPH and WBPH cannot. In addition, other genes related with moulting, and membrane lipid composition might also play roles in resistance to low and high temperatures. Our study illustrates the common responses and different tolerance mechanisms of three rice planthoppers in coping with temperature change, and provides a potential strategy for pest management.

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tumor Targeting Synergistic Drug Delivery by Self-Assembled Hybrid Nanovesicles to Overcome Drug Resistance - Meng-Qing Gong; Cong Wu; Xiao-Yan He; Jing-Yi Zong; Jin-Long Wu; Ren-Xi Zhuo; Si-Xue Cheng (Pharmaceutical Research, 2017)

Microglia Activation and Polarization After Intracerebral Hemorrhage in Mice: the Role of Protease-Activated Receptor-1 - Shu Wan; Yingying Cheng; Hang Jin; Dewei Guo; Ya Hua; Richard F. Keep; Guohua Xi (Translational Stroke Research, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

The Effect of Substrate Stiffness on Cardiomyocyte Action Potentials - Sean D. Boothe; Jackson D. Myers; Seokwon Pok; Junping Sun; Yutao Xi; Raymond M Nieto; Jie Cheng; Jeffrey G. Jacot (Cell Biochemistry and Biophysics, 2016)

Joint probability of precipitation and reservoir storage for drought estimation in the headwater basin of the Huaihe River, China - Runrun Zhang; Xi Chen; Qinbo Cheng; Zhicai Zhang; Peng Shi (Stochastic Environmental Research and Risk Assessment, 2016)

Relationships between foliar carbon isotope composition and elements of C3 species in grasslands of Inner Mongolia, China - Yong-Chun Zhou; Xi-Lei Cheng; Jiang-Wen Fan; Warwick Harris (Plant Ecology, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Physiological controls of chrysanthemum DgD27 gene expression in regulation of shoot branching - Chao Wen; Qingcui Zhao; Jing Nie; Guoqin Liu; Lin Shen; Chenxia Cheng; Lin Xi; Nan Ma; Liangjun Zhao (Plant Cell Reports, 2016)

Plasma Homocysteine Levels Predict the Risk of Acute Cerebral Infarction in Patients with Carotid Artery Lesions - Wei Wu; Yi Guan; Kan Xu; Xi-Jia Fu; Xiao-Feng Lei; Li-Jian Lei; Zhi-Qing Zhang; Yan Cheng; Yun-Qian Li (Molecular Neurobiology, 2016)

Isolation and characterization of cDNAs and genomic DNAs encoding ADP-glucose pyrophosphorylase large and small subunits from sweet potato - Yu-Xi Zhou; Yu-Xiang Chen; Xiang Tao; Xiao-Jie Cheng; Hai-Yan Wang (Molecular Genetics and Genomics, 2016)

Changes in inland lakes on the Tibetan Plateau over the past 40 years - Yue Fang; Weiming Cheng; Yichi Zhang; Nan Wang; Shangmin Zhao; Chenghu Zhou; Xi Chen; Anming Bao (Journal of Geographical Sciences, 2016)

Effects of TGF-β1 on the Proliferation and Apoptosis of Human Cervical Cancer Hela Cells In Vitro - Ming-Zhu Tao; Xia Gao; Tie-Jun Zhou; Qing-Xi Guo; Qiang Zhang; Cheng-Wan Yang (Cell Biochemistry and Biophysics, 2015)

Adaptive Allocation Modeling for a Complex System of Regional Water and Land Resources Based on Information Entropy and its Application - Kun Cheng; Qiang Fu; Xi Chen; Tianxiao Li; Qiuxiang Jiang; Xiaosong Ma; Ke Zhao (Water Resources Management, 2015)

Neuroprotective effect of bisabolangelone on hydrogen peroxide-induced neurotoxicity in SH-SY5Y cells - Jun-Zhi Wang; Xi-Ming Yan; Zi-Cheng Li; Hua-Jun Luo; Nian-Yu Huang; Wei-Qiao Deng (Medicinal Chemistry Research, 2015)

MicroRNA expression profile of mature dendritic cell in chronic rhinosinusitis - Zu-Xia Ma; Xi Tan; Yang Shen; Xia Ke; Yu-Cheng Yang; Xing-Bo He; Zhi-Hai Wang; Yu-Bing Dai; Su-Ling Hong; Guo-Hua Hu (Inflammation Research, 2015)

Wild soybean roots depend on specific transcription factors and oxidation reduction related genesin response to alkaline stress - Huizi DuanMu; Yang Wang; Xi Bai; Shufei Cheng; Michael K. Deyholos; Gane Ka-Shu Wong; Dan Li; Dan Zhu; Ran Li; Yang Yu; Lei Cao; Chao Chen; et al. (Functional & Integrative Genomics, 2015)

Impact of diethylhexyl phthalate on gene expression and development of mammary glands of pregnant mouse - Lan Li; Jing-Cai Liu; Yong Zhao; Fang-Nong Lai; Fan Yang; Wei Ge; Cheng-Li Dou; Wei Shen; Xi-Feng Zhang; Hong Chen (Histochemistry and Cell Biology, 2015)

Physiological and genetic analyses reveal a mechanistic insight into the multifaceted lifestyles of P seudoalteromonas sp. SM 9913 adapted to the deep‐sea sediment - Zi‐Hao Mi; Zi‐Chao Yu; Hai‐Nan Su; Lei Wang; Xiu‐Lan Chen; Xiuhua Pang; Qi‐Long Qin; Bin‐Bin Xie; Xi‐Ying Zhang; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2015)
Summary Although bacteriobenthos play a major role in the degradation of particulate organic matter in marine sediment, knowledge of the sediment‐adapted lifestyles of bacteriobenthos is still scarce. Here, the particle‐associated, swimming and swarming lifestyles of the benthonic bacterium P seudoalteromonas sp. SM 9913 ( SM 9913) were illustrated. SM 9913 had a clay particle‐associated lifestyle, and its exopolysaccharide played an important role in this lifestyle. SM 9913 also had swimming and swarming motilities, indicating that it may have swimming and swarming lifestyles in the sediment. The lateral flagella were responsible for the swarming motility, and the polar flagella were responsible for the swimming motility. Iron limitation was an indispensable inductive signal of the swarming motility. An analysis of the motilities of SM 9913 and its mutants in clay demonstrated that SM 9913 moved in clay by both swimming and swarming motilities. Genomic analysis suggests that having two flagella systems is most likely a common adaptation of some bacteriobenthos to the sediment environment. Our results reveal the lifestyles of benthonic SM 9913, providing a better understanding of the environmental adaptation of benthonic bacteria.

Erratum to: Functional Characterization of a Putative Bacterial Wilt Resistance Gene (RE-bw) in Eggplant - Xiao Xi’ou; Li Guannan; Cao Bihao; Lei Jianjun; Chen Qinghua; Jiang Jin; Cheng Yujing (Plant Molecular Biology Reporter, 2015)

Functional Characterization of a Putative Bacterial Wilt Resistance Gene (RE-bw) in Eggplant - Xiao Xi’ou; Cao Bihao; Li Guannan; Lei Jianjun; Chen Qinghua; Jiang Jin; Cheng Yujing (Plant Molecular Biology Reporter, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Cadmium contamination of rice from various polluted areas of China and its potential risks to human health - Shen Ke; Xi-Yu Cheng; Ni Zhang; Hong-Gang Hu; Qiong Yan; Ling-Ling Hou; Xin Sun; Zhi-Nan Chen (Environmental Monitoring and Assessment, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Tissue lipid metabolism and hepatic metabolomic profiling in response to supplementation of fermented cottonseed meal in the diets of broiler chickens - Cun-xi Nie; Wen-ju Zhang; Yong-qiang Wang; Yan-feng Liu; Wen-xia Ge; Jian-cheng Liu (Journal of Zhejiang University-SCIENCE B, 2015)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Reconstruction of statistical–dynamical model of the Western Pacific subtropical high and East Asian summer monsoon factors and its forecast experiments - Mei Hong; Ren Zhang; Cheng Zu Bai; Xi Chen; Dong Wang; Jingjing Ge (Natural Hazards, 2015)

Neurochemical properties of the synapses between the parabrachial nucleus-derived CGRP-positive axonal terminals and the GABAergic neurons in the lateral capsular division of central nucleus of amygdala - Ya-Cheng Lu; Yan-Zhou Chen; Yan-Yan Wei; Xiao-Tao He; Xia Li; Wei Hu; Yuchio Yanagawa; Wen Wang; Sheng-Xi Wu; Yu-Lin Dong (Molecular Neurobiology, 2015)

Forest canopy height mapping over China using GLAS and MODIS data - Ting Yang; Cheng Wang; GuiCai Li; SheZhou Luo; XiaoHuan Xi; Shuai Gao; HongCheng Zeng (Science China Earth Sciences, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Rainfall and tillage impacts on soil erosion of sloping cropland with subtropical monsoon climate — A case study in hilly purple soil area, China - Jia-liang Tang; Xun-qiang Cheng; Bo Zhu; Mei-rong Gao; Tao Wang; Xi-feng Zhang; Pei Zhao; Xiang You (Journal of Mountain Science, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Genome-wide identification and expression profiling of DNA methyltransferase gene family in maize - Yexiong Qian; Yilong Xi; Beijiu Cheng; Suwen Zhu (Plant Cell Reports, 2014)

Synergistic effects of TAL1 over-expression and PHO13 deletion on the weak acid inhibition of xylose fermentation by industrial Saccharomyces cerevisiae strain - Yun-Cheng Li; Zi-Xi Gou; Ze-Shen Liu; Yue-Qin Tang; Takashi Akamatsu; Kenji Kida (Biotechnology Letters, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Thrombin-Induced Cerebral Hemorrhage: Role of Protease-Activated Receptor-1 - Yingying Cheng; Guohua Xi; Hang Jin; Richard F. Keep; Jiachun Feng; Ya Hua (Translational Stroke Research, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

New phenotypic characteristics of three tmm alleles in Arabidopsis thaliana - Longfeng Yan; Xi Cheng; Ruiling Jia; Qianqian Qin; Liping Guan; Hang Du; Suiwen Hou (Plant Cell Reports, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Impacts of Lactobacillus plantarum in Depuration for Reducing Vibrio parahaemolyticus in Pacific Oysters ( Crassostrea gigas ) - Dunyu Xi; Chengchu Liu; Yi-Cheng Su (Journal of Aquatic Food Product Technology, 2014)

Identification and characterization of the SET domain gene family in maize - Yexiong Qian; Yilong Xi; Beijiu Cheng; Suwen Zhu; Xianzhao Kan (Molecular Biology Reports, 2014)

Transcriptome and Gene Expression Analysis of an Oleaginous Diatom Under Different Salinity Conditions - Ruo-lin Cheng; Jia Feng; Bing-Xin Zhang; Yun Huang; Jun Cheng; Chuan-Xi Zhang (BioEnergy Research, 2014)

Identification of QTLs with additive, epistatic and QTL × development interaction effects for seed dormancy in rice - Ling Wang; Jinping Cheng; Yanyan Lai; Wenli Du; Xi Huang; Zhoufei Wang; Hongsheng Zhang (Planta, 2014)

Karyotype of mitotic metaphase and meiotic diakinesis in non-heading Chinese cabbage - Jin-shuang Zheng; Cheng-zhen Sun; Shu-ning Zhang; Xi-lin Hou (Plant Systematics and Evolution, 2014)

Topographic characteristics for the geomorphologic zones in the northwestern edge of the Qinghai-Tibet Plateau - Wei-ming Cheng; Shang-min Zhao; Cheng-hu Zhou; Xi Chen (Journal of Mountain Science, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Common genetic variants associated with lipid profiles in a Chinese pediatric population - Yue Shen; Bo Xi; Xiaoyuan Zhao; Hong Cheng; Dongqing Hou; Lijun Wu; Xingyu Wang; Jie Mi (Human Genetics, 2013)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Performance of hybrid vertical up- and downflow subsurface flow constructed wetlands in treating synthetic high-strength wastewater - Yong-Jun Zhao; Pu Cheng; Xi Pei; Hui Zhang; Cheng Yan; Shou-Bing Wang (Environmental Science and Pollution Research, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Circulating IL-21 levels increase during early simian-human immunodeficiency virus infection in macaques - Chang-cheng Zhao; Jing Xue; Zhe Cong; Xi-qiang Gao; Wei-lun Zhang; Ting Chen; Fang-xin Wu; Jing Xiong; Bin Ju; Aihua Su; Qiang Wei; Chuan Qin (Archives of Virology, 2013)

Effects of stand structure on wind speed reduction in a Metasequoia glyptostroboides shelterbelt - Tonggui Wu; Mukui Yu; Geoff Wang; Zongxing Wang; Xi Duan; Yi Dong; Xiangrong Cheng (Agroforestry Systems, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Effects of dexamethasone and Salvia miltiorrhiza on multiple organs in rats with severe acute pancreatitis - Jing-min Ou; Xi-ping Zhang; Cheng-jun Wu; Di-jiong Wu; Ping Yan (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Enhanced apoptosis in retinal pigment epithelium under inflammatory stimuli and oxidative stress - Yujuan Wang; Defen Shen; Vinson M. Wang; Cheng-Rong Yu; Ren-Xi Wang; Jingsheng Tuo; Chi-Chao Chan (Apoptosis, 2012)

Pretreatment with anti-flagellin serum delays acute lung injury in rats with sepsis - Ming-Dong Hu; Yu Yang; Chang-Xi Zhou; Qi Li; Wang Yi; Gui-Sheng Qian; Mei Mao; Jian-Cheng Xu (Inflammation Research, 2012)

Differential expression of Rs-eng-1b in two populations of Radopholus similis (Tylenchida: Pratylecnchidae) and its relationship to pathogenicity - Chao Zhang; Hui Xie; Chun-Ling Xu; Xi Cheng; Ke-Mei Li; Yu Li (European Journal of Plant Pathology, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Bombyx mori nucleopolyhedrovirus ORF54, a viral desmoplakin gene, is associated with the infectivity of budded virions - Min-Juan Zhang; Cai-Hong Tian; Xiao-Ying Fan; Yi-Han Lou; Ruo-Lin Cheng; Chuan-Xi Zhang (Archives of Virology, 2012)

PEG-Stabilized Micellar System with Positively Charged Polyester Core for Fast pH-Responsive Drug Release - Hua-Fen Wang; Hui-Zhen Jia; Si-Xue Cheng; Jun Feng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2012)

Analysis of expressed sequence tags from grapevine flower and fruit and development of simple sequence repeat markers - Xi-Cheng Wang; Lei Guo; Ling-Fei Shangguan; Chen Wang; Guang Yang; Shen-Chun Qu; Jing-Gui Fang (Molecular Biology Reports, 2012)

Association between MTHFR C677T polymorphism and osteonecrosis of the femoral head: a meta-analysis - Xi-fu Shang; Hong Su; Wei-wei Chang; Chen-cheng Wang; Qin Han; Zhi-wei Xu (Molecular Biology Reports, 2012)

Hypothesis: Human Umbilical Cord Blood-Derived Stromal Cells Regulate the Foxp3 Expression of Regulatory T Cells Through the TGF-β1/Smad3 Pathway - Cheng Zhang; Xi Zhang; Xing-Hua Chen (Cell Biochemistry and Biophysics, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Trend analysis of building height and total floor space in Beijing, China using ICESat/GLAS data - Feng Cheng; Cheng Wang; Jinliang Wang; Fuxin Tang; Xiaohuan Xi (International Journal of Remote Sensing, 2011)

Accuracy assessment of the ASTER GDEM and SRTM3 DEM: an example in the Loess Plateau and North China Plain of China - Shangmin Zhao; Weiming Cheng; Chenghu Zhou; Xi Chen; Shifang Zhang; Zengpo Zhou; Haijiang Liu; Huixia Chai (International Journal of Remote Sensing, 2011)

The embryo rescue derived intergeneric hybrid between chrysanthemum and Ajania przewalskii shows enhanced cold tolerance - Yanming Deng; Sumei Chen; Fadi Chen; Xi Cheng; Fei Zhang (Plant Cell Reports, 2011)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Synthesis and antidepressant-like action of N-(2-hydroxyethyl) cinnamamide derivatives in mice - Xian-Qing Deng; Di Wu; Cheng-Xi Wei; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Synthesis and evaluation of 7-substituted-3,4-dihydrobenzo[f][1,4]oxazepin-5(2H)-ones as anticonvulsant and hypnotic agents - Xian-Qing Deng; Ming-Xia Song; Cheng-Xi Wei; Zhi-Gang Sun; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

The launch of a large regional gravity information system in China - Ming-Hua Zhang; Hao He; Cheng-Xi Wang (Applied Geophysics, 2011)

Enantioselective Fluorescent Sensors for Amino Acid Derivatives Based on BINOL Bearing S-tryptophan Unit: Synthesis and Chiral Recognition - Kuo-Xi Xu; Peng-Fei Cheng; Jin Zhao; Chao-Jie Wang (Journal of Fluorescence, 2011)

Rich allelic variations of Viviparous-1A and their associations with seed dormancy/pre-harvest sprouting of common wheat - Cheng Chang; Hai-Ping Zhang; Qiu-Xia Zhao; Ji-Ming Feng; Hong-Qi Si; Jie Lu; Chuan-Xi Ma (Euphytica, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Characterization of a male sterile mutant from progeny of a transgenic plant containing a leaf senescence-inhibition gene in wheat - Ya-Jun Xi; Xue-Feng Ma; Huan Zhong; Shu-Dong Liu; Zhu-Lin Wang; Yang-Yang Song; Cheng-Hui Zhao (Euphytica, 2011)

Creating novel chrysanthemum germplasm via interspecific hybridization and backcrossing - Xi Cheng; Sumei Chen; Fadi Chen; Yanming Deng; Weimin Fang; Fangping Tang; Zhaolei Liu; Wei Shao (Euphytica, 2011)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

Proteomic analysis of cell lines to identify the irinotecan resistance proteins - Xing-Chen Peng; Feng-Ming Gong; Meng Wei; Xi Chen; Ye Chen; Ke Cheng; Feng Gao; Feng Xu; Feng Bi; Ji-Yan Liu (Journal of Biosciences, 2010)

The supramolecular architecture, function, and regulation of thylakoid membranes in red algae: an overview - Hai-Nan Su; Bin-Bin Xie; Xi-Ying Zhang; Bai-Cheng Zhou; Yu-Zhong Zhang (Photosynthesis Research, 2010)

Synthesis of 6-(3-substituted-4H-1,2,4-triazol-4-yl)-2-phenylbenzo[d]oxazoles as potential anticonvulsant agents - Cheng-Xi Wei; Di Wu; Zhi-Gang Sun; Kyu-Yun Chai; Zhe-Shan Quan (Medicinal Chemistry Research, 2010)

Construction and Preliminary Analysis of a Deep-Sea Sediment Metagenomic Fosmid Library from Qiongdongnan Basin, South China Sea - Yongfei Hu; Chengzhang Fu; Yeshi Yin; Gong Cheng; Fang Lei; Xi Yang; Jing Li; Elizabeth Jane Ashforth; Lixin Zhang; Baoli Zhu (Marine Biotechnology, 2010)

Using chimeric piggyBac transposase to achieve directed interplasmid transposition in silkworm Bombyx mori and fruit fly Drosophila cells - Na Wang; Cai-ying Jiang; Ming-xing Jiang; Chuan-xi Zhang; Jia-an Cheng (Journal of Zhejiang University-SCIENCE B, 2010)

Hydrogen sulfide protects soybean seedlings against drought-induced oxidative stress - Hua Zhang; Hao Jiao; Cheng-Xi Jiang; Song-Hua Wang; Zhao-Jun Wei; Jian-Ping Luo; Russell L. Jones (Acta Physiologiae Plantarum, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Interspecific hybrids between Dendranthema morifolium (Ramat.) Kitamura and D. nankingense (Nakai) Tzvel. achieved using ovary rescue and their cold tolerance characteristics - Xi Cheng; Sumei Chen; Fadi Chen; Weimin Fang; Yanming Deng; Linfang She (Euphytica, 2010)

Efficient separation and purification of allophycocyanin from Spirulina (Arthrospira) platensis - Hai-Nan Su; Bin-Bin Xie; Xiu-Lan Chen; Jin-Xia Wang; Xi-Ying Zhang; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2010)

Heterologous expression of a hydrogenase gene in Enterobacter aerogenes to enhance hydrogen gas production - Jin-Fang Zhao; Wen-Lu Song; Jun Cheng; Chuan-Xi Zhang (World Journal of Microbiology and Biotechnology, 2010)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Phylogenetic analysis of 16S rRNA gene sequences reveals rumen bacterial diversity in Yaks (Bos grunniens) - L. Y. Yang; J. Chen; X. L. Cheng; D. M. Xi; S. L. Yang; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2010)

Isolation of a low-sulfur tolerance gene from Eichhornia crassipes using a functional gene-mining approach - Xiao Liu; Xi Chen; David J. Oliver; Cheng-Bin Xiang (Planta, 2009)

Bacteremia due to Rhodococcus equi: a case report and review of the literature - Xi-yuan Chen; Feng Xu; Jing-yan Xia; Yu-sheng Cheng; Yan Yang (Journal of Zhejiang University-SCIENCE B, 2009)

Digital regionalization of geomorphology in Xinjiang - Huixia Chai; Chenghu Zhou; Xi Chen; Weiming Cheng (Journal of Geographical Sciences, 2009)

A Potential Targeting Gene Vector Based on Biotinylated Polyethyleneimine/Avidin Bioconjugates - Xuan Zeng; Yun-Xia Sun; Xian-Zheng Zhang; Si-Xue Cheng; Ren-Xi Zhuo (Pharmaceutical Research, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Ecological risk assessment of open coal mine area - Ma Xi-jun; Lu Zhao-hua; Cheng Jian-long (Environmental Monitoring and Assessment, 2008)

Enhancement of phenylethanoid glycosides biosynthesis in cell cultures of Cistanche deserticola by osmotic stress - Chun-Zhao Liu; Xi-Yu Cheng (Plant Cell Reports, 2008)

Establishment and characterization of two embryonic cell lines of Bombyx mori - Min-Hui Pan; Shi-Quan Xiao; Min Chen; Xi-Jun Hong; Cheng Lu (In Vitro Cellular & Developmental Biology - Animal, 2007)

Scaling behavior of nucleotide cluster in DNA sequences - Jun Cheng; Zi-shuang Tong; Lin-xi Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Statistical properties of nucleotide clusters in DNA sequences - Jun Cheng; Lin-xi Zhang (Journal of Zhejiang University-SCIENCE B, 2005)

Purification and some properties of ?-N-acetyl-D-glucosaminidase from prawn (Penaeus vannamei) - Xiao-Lan Xie; Qing-Xi Chen; Jian-Cheng Lin; Yue Wang (Marine Biology, 2004)

Triplet Excitation Transfer between Carotenoids in the LH2 Complex from Photosynthetic Bacterium Rhodopseudomonas palustris - Juan Feng; Qian Wang; Yi-Shi Wu; Xi-Cheng Ai; Xu-Jia Zhang; You-Guo Huang; Xing-Kang Zhang; Jian-Ping Zhang (Photosynthesis Research, 2004)

Complex influence of rice variety, fertilization timing, and insecticide on population dynamics of Sogatella furcifera (Horvath) , Nilaparvata lugens (Stl) (Homoptera: Delphacidae) and their natural enemies in rice in Hangzhou, China - Zeng-Rong Zhu; Jiaan Cheng; Ming-Xing Jiang; Xiao-Xi Zhang (Journal of Pest Science, 2004)

Synthesis, protein-binding ability and phytoalexin-elicitor activity of epoxyalkyl (1→3)-β-D-oligoglucosides - Gang-Liang Huang; Man-Xi Liu; Xin-Ya Mei; Yuan-Cheng Cao (Glycoconjugate Journal, 2003)

Arbuscular mycorrhizal status of plants and the spore density of arbuscular mycorrhizal fungi in the tropical rain forest of Xishuangbanna, southwest China - Zhi-Wei Zhao; Yong-Mei Xia; Xin-Zheng Qin; Xi-Wu Li; Li-Zhong Cheng; Tao Sha; Guo-Hua Wang (Mycorrhiza, 2001)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)